Photocurable composition and dental product
By adjusting the adhesion and hardness of the photocurable composition, the problem of deformation and discomfort in use of dental products is solved, and higher stability and wear comfort are achieved.
Patent Information
- Application Number
- CN202080068277.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-04-13
- Filing Date
- 2020-10-28
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2040-10-28
AI Technical Summary
Dental products are prone to cracks and cracks due to deformation during use, and are poor in operability and may cause discomfort and pain during use.
A photocurable composition containing (meth)acrylic monomer and a photopolymerization initiator has been developed to suppress deformation and discomfort by adjusting its adhesion, elongation of break, impact absorption and Shore A hardness. , and improve operability.
It is achieved without damaging the strength and hardness of the dental products, and the occurrence of cracks and cracks are suppressed, and the operability and wear comfort are improved.
Smart Images

Figure CN114514255B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a photocurable composition and a dental article. Background Art
[0002] Currently, resins are used in a variety of applications and are required to have properties that match the application. For example, dental braces are used for treatment of temporomandibular joint disease and orthodontic treatment.
[0003] In recent years, dental products include dental restorations, devices used in the oral cavity (mouth guards, etc.), and other dental products (gum guards, etc.), and various materials are used according to their respective uses.
[0004] For example, Patent Document 1 discloses a composition for a tooth guard, characterized in that it contains: A) a styrene block copolymer; B) at least one thermoplastic resin selected from the group consisting of alicyclic saturated hydrocarbon resins, terpene resins, and aliphatic petroleum resins; and C) at least one wax selected from the group consisting of mineral waxes, synthetic waxes, plant waxes, and animal waxes.
[0005] Patent Document 1: Japanese Patent Application Publication No. 2003-019240 Summary of the invention
[0006] Problems to be solved by the invention
[0007] For example, dental products such as sports mouthpieces often deform due to use of the products. In addition, the deformed product may not recover after use and may crack or break. Therefore, there is a tendency to demand materials that can suppress these problems. In addition, dental products such as sports mouthpieces may have high adhesion when using the products, so the handling properties may be impaired.
[0008] Problem A to be solved by the first embodiment of the present disclosure is to provide a photocurable composition that can obtain a cured product with excellent workability and in which the occurrence of cracks and fissures is suppressed, and a dental product having the cured product of the photocurable composition.
[0009] In addition, when using dental products such as mouthpieces, some force may be applied to the contact surface between the teeth and the dental product, causing discomfort. The discomfort may often manifest as pain or other discomfort.
[0010] The discomfort described above may often become a problem when using dental products, and improvement is desired.
[0011] Problem B to be solved by the second embodiment of the present disclosure is to provide a photocurable composition that can provide a cured product that has excellent workability and suppresses discomfort when applied to the human body, and a dental product having the cured product of the photocurable composition.
[0012] Methods for solving problems
[0013] Specific methods for solving at least one of the above-mentioned problem A and the above-mentioned problem B include the following aspects.
[0014] The first embodiment is exemplified by the photocurable composition described in the following <1>.
[0015] The second embodiment is exemplified by the photocurable composition described in the following <6>.
[0016] <1> A photocurable composition comprising a (meth)acrylic monomer component and a photopolymerization initiator, wherein the adhesive force of a cured product is 1.5 N or less and the elongation at break of the cured product is 20% or more.
[0017] <2> The photocurable composition according to <1>, wherein the cured product has an elongation at break of 40% or more.
[0018] <3> A photocurable composition comprising a (meth)acrylic monomer component and a photopolymerization initiator, wherein the adhesive force of a cured product is 1.5 N or less, and the impact absorbency of the cured product is 20% or more and 80% or less.
[0019] <4> The photocurable composition according to <3>, wherein the impact absorption of the cured product is 20% to 70%.
[0020] <5> The photocurable composition according to <3> or <4>, wherein the cured product has an elongation at break of 20% or more.
[0021] <6> A photocurable composition comprising a (meth)acrylic monomer component and a photopolymerization initiator, wherein the adhesive force of a cured product thereof is 1.5 N or less, and the Shore A hardness of the cured product thereof is 97 or less.
[0022] <7> The photocurable composition according to any one of <1> to <6>, wherein the aromatic ring concentration in the (meth)acrylic monomer component is 0.00100 mol / g or more.
[0023] <8> The photocurable composition according to any one of <1> to <7>, wherein the (meth)acrylic monomer component comprises a (meth)acrylic monomer (A) having two (meth)acryloyl groups and a (meth)acrylic monomer (B) having one (meth)acryloyl group.
[0024] <9> The photocurable composition according to <8>, wherein at least one of the (meth)acrylic monomer (A) and the (meth)acrylic monomer (B) has an aromatic group.
[0025] <10> A photocurable composition comprising a (meth)acrylic monomer component and a photopolymerization initiator, wherein the (meth)acrylic monomer component comprises a (meth)acrylic monomer (A) having two (meth)acryloyl groups and a (meth)acrylic monomer (B) having one (meth)acryloyl group, wherein the molecular weight of the (meth)acrylic monomer (A) per one (meth)acryloyl group is 300 g / mol or more, and at least one of the (meth)acrylic monomer (A) and the (meth)acrylic monomer (B) has an aromatic group.
[0026] <11> The photocurable composition according to any one of <8> to <10>, wherein the content of the (meth)acrylic monomer (A) is 250 to 800 parts by mass based on 1000 parts by mass of the total content of the (meth)acrylic monomer (A) and the (meth)acrylic monomer (B).
[0027] <12> The photocurable composition according to any one of <8> to <11>, wherein the (meth)acrylic monomer (A) includes a compound represented by the following formula (1).
[0028] [Chemistry 1]
[0029]
[0030] (In formula (1), R 1 and R 2 Each independently represents a divalent linking group, R 3 are each independently a methyl group or a hydrogen atom.)
[0031] <13> The photocurable composition according to <12>, wherein the R 1 It is a divalent chain hydrocarbon group, or a group consisting of a divalent chain hydrocarbon group and at least one group selected from the group consisting of a divalent hydrocarbon group having an alicyclic structure, a divalent hydrocarbon group having an aromatic structure and a divalent group containing a heteroatom, wherein the aforementioned divalent hydrocarbon group having an aromatic structure is a divalent hydrocarbon group represented by the following formula (1-a).
[0032] [Chemistry 2]
[0033]
[0034] (In formula (1-a), * indicates a binding position.)
[0035] <14> The photocurable composition according to <12>, wherein the R 1 It is a divalent chain hydrocarbon group, or a group consisting of a divalent chain hydrocarbon group and at least one group selected from the group consisting of a divalent hydrocarbon group having an alicyclic structure and a divalent group containing a heteroatom.
[0036] <15> The photocurable composition according to <13> or <14>, wherein R 1 The heteroatom-containing divalent group in includes at least one bond selected from the group consisting of a urethane bond and an ether bond.
[0037] <16> The photocurable composition according to any one of <8> to <15>, which satisfies at least one of the following (a) and (b).
[0038] (a) The (meth)acrylic monomer (A) comprises a (meth)acrylic monomer (A-1) having a molecular weight of 300 g / mol to 600 g / mol per (meth)acryloyl group, and a (meth)acrylic monomer (A-2) having a molecular weight of more than 600 g / mol to 15,000 g / mol per (meth)acryloyl group.
[0039] (b) The (meth)acrylic monomer (B) includes a (meth)acrylic monomer (B-1) having two aromatic rings and a (meth)acrylic monomer (B-2) having one aromatic ring.
[0040] <17> The photocurable composition according to any one of <8> to <16>, wherein the aromatic ring concentration in the (meth)acrylic monomer (A) is 0.0016 mol / g or less.
[0041] <18> The photocurable composition according to any one of <8> to <17>, wherein the total content of the (meth)acrylic monomer (A) and the (meth)acrylic monomer (B) in the (meth)acrylic monomer component is 90% by mass or more.
[0042] <19> The photocurable composition according to any one of <7> to <18>, wherein Z1 obtained by the following formula β is 1×10 4 ~100×10 4 .
[0043] Z1=X1 / Y1 Formula β
[0044] X1 (g / mol): Molecular weight of the (meth)acrylic monomer (A) per (meth)acryloyl group
[0045] Y1 (mol / g): Aromatic ring concentration in the (meth)acrylic monomer component
[0046] <20> The photocurable composition according to any one of <1> to <19>, which has a viscosity of 10 to 5000 mPa·s at 25° C. and 50 rpm as measured by an E-type viscometer.
[0047] <21> The photocurable composition according to any one of <1> to <20>, which is for photomodeling.
[0048] <22> The photocurable composition according to any one of <1> to <21>, which is used for producing a dental product by photomolding.
[0049] <23> The photocurable composition according to any one of <1> to <22>, which is used for producing a dental cap, a gum cover or a lining material by photomolding.
[0050] <24> A dental product comprising a cured product of the photocurable composition according to any one of <1> to <23>.
[0051] <25> The dental product according to <24>, which is for use as a dental cap, a gum mask, or a lining material.
[0052] <26> A method for producing three-dimensional image data of a mouth guard, comprising: producing three-dimensional image data of a mouth guard in which the thickness of an occlusal surface of a central incisor portion is 1.5 times or more the thickness of an occlusal surface of a second molar portion.
[0053] <27> In the method for creating three-dimensional image data of a mouth guard according to <26>, the thickness of the occlusal surface of the central incisor portion is not more than 5 times the thickness of the occlusal surface of the second molar portion.
[0054] <28> A method for manufacturing a mouth guard, comprising: a process of producing three-dimensional image data of a mouth guard by the method for producing three-dimensional image data of a mouth guard described in <26> or <27>; and a process of manufacturing the mouth guard by light modeling using the produced three-dimensional image data of the aforementioned mouth guard.
[0055] Specific means for solving the above-mentioned problem A include the following aspects.
[0056] <1A> A photocurable composition comprising a (meth)acrylic monomer component and a photopolymerization initiator, wherein the adhesive force of a cured product is 1.5 N or less and the elongation at break of the cured product is 20% or more.
[0057] <2A> The photocurable composition according to <1A>, wherein the cured product has an elongation at break of 40% or more.
[0058] <3A> A photocurable composition comprising a (meth)acrylic monomer component and a photopolymerization initiator, wherein the adhesive force of a cured product is 1.5 N or less, and the impact absorbency of the cured product is 20% or more and 80% or less.
[0059] <4A> The photocurable composition according to <3A>, wherein the impact absorbency of the cured product is 20% to 70%.
[0060] <5A> The photocurable composition according to <3A> or <4A>, wherein the cured product has an elongation at break of 20% or more.
[0061] <6A> The photocurable composition according to any one of <1A> to <5A>, wherein the (meth)acrylic monomer component comprises a (meth)acrylic monomer (A) having two (meth)acryloyl groups and a (meth)acrylic monomer (B) having one (meth)acryloyl group.
[0062] <7A> The photocurable composition according to <6A>, wherein at least one of the (meth)acrylic monomer (A) and the (meth)acrylic monomer (B) has an aromatic group.
[0063] <8A> A photocurable composition comprising a (meth)acrylic monomer component and a photopolymerization initiator, wherein the (meth)acrylic monomer component comprises a (meth)acrylic monomer (A) having two (meth)acryloyl groups and a (meth)acrylic monomer (B) having one (meth)acryloyl group, wherein the molecular weight of the (meth)acrylic monomer (A) per one (meth)acryloyl group is 300 g / mol or more, and at least one of the (meth)acrylic monomer (A) and the (meth)acrylic monomer (B) has an aromatic group.
[0064] <9A> The photocurable composition according to any one of <6A> to <8A>, wherein the content of the (meth)acrylic monomer (A) is 250 to 800 parts by mass relative to 1000 parts by mass of the total content of the (meth)acrylic monomer (A) and the (meth)acrylic monomer (B).
[0065] <10A> The photocurable composition according to any one of <6A> to <9A>, wherein the total content of the (meth)acrylic monomer (A) and the (meth)acrylic monomer (B) in the (meth)acrylic monomer component is 90% by mass or more.
[0066] <11A> The photocurable composition according to any one of <6A> to <10A>, wherein the (meth)acrylic monomer (A) includes a urethane bond.
[0067] <12A> The photocurable composition according to any one of <1A> to <11A>, wherein the aromatic ring concentration in the (meth)acrylic monomer component is 0.00100 mol / g or more.
[0068] <13A> The photocurable composition according to any one of <1A> to <12A>, wherein the viscosity measured by an E-type viscometer at 25° C. and 50 rpm is 10 mPa·s to 5000 mPa·s.
[0069] <14A> The photocurable composition according to any one of <1A> to <13A>, which is for photomodeling.
[0070] <15A> The photocurable composition according to any one of <1A> to <14A>, which is used for producing a dental product by photomolding.
[0071] <16A> The photocurable composition according to any one of <1A> to <15A>, which is used for producing a dental cap or a gum mask by photomolding.
[0072] <17A> A dental product comprising a cured product of the photocurable composition according to any one of <1A> to <16A>.
[0073] <18> The dental product according to <17>, which is for use as a dental cap or a gum mask.
[0074] Specific methods for solving the above-mentioned problem B include the following aspects.
[0075] <1B> A photocurable composition comprising a (meth)acrylic monomer component and a photopolymerization initiator, wherein the adhesive force of a cured product is 1.5 N or less, and the Shore A hardness of the cured product is 97 or less.
[0076] <2B> The photocurable composition according to <1B>, wherein the (meth)acrylic monomer component includes a (meth)acrylic monomer (A) having two (meth)acryloyl groups and a (meth)acrylic monomer (B) having one (meth)acryloyl group.
[0077] <3B> The photocurable composition according to <2B>, wherein at least one of the (meth)acrylic monomer (A) and the (meth)acrylic monomer (B) has an aromatic group.
[0078] <4B> A photocurable composition comprising a (meth)acrylic monomer component and a photopolymerization initiator, wherein the (meth)acrylic monomer component comprises a (meth)acrylic monomer (A) having two (meth)acryloyl groups and a (meth)acrylic monomer (B) having one (meth)acryloyl group, the molecular weight of the (meth)acrylic monomer (A) per one (meth)acryloyl group being 300 g / mol or more, at least one of the (meth)acrylic monomer (A) and the (meth)acrylic monomer (B) having an aromatic group, and the Shore A hardness of the cured product being 97 or less.
[0079] <5B> The photocurable composition according to any one of <2B> to <4B>, wherein the content of the (meth)acrylic monomer (A) is 250 to 800 parts by mass based on 1000 parts by mass of the total content of the (meth)acrylic monomer (A) and the (meth)acrylic monomer (B).
[0080] <6B> The photocurable composition according to any one of <2B> to <5B>, wherein the total content of the (meth)acrylic monomer (A) and the (meth)acrylic monomer (B) in the (meth)acrylic monomer component is 90% by mass or more.
[0081] <7B> The photocurable composition according to any one of <2B> to <6B>, wherein the (meth)acrylic monomer (A) includes a urethane bond.
[0082] <8B> The photocurable composition according to any one of <1B> to <7B>, wherein the cured product has a Shore A hardness of 50 or more.
[0083] <9B> The photocurable composition according to any one of <1B> to <8B>, wherein the aromatic ring concentration in the (meth)acrylic monomer component is 0.00100 mol / g or more.
[0084] <10B> The photocurable composition according to any one of <1B> to <9B>, wherein the viscosity measured by an E-type viscometer at 25° C. and 50 rpm is 10 mPa·s to 5000 mPa·s.
[0085] <11B> The photocurable composition according to any one of <1B> to <10B>, which is for photomodeling.
[0086] <12B> The photocurable composition according to any one of <1B> to <11B>, which is used for producing a dental product by photomolding.
[0087] <13B> The photocurable composition according to any one of <1B> to <12B>, which is used for producing a dental cap or a lining material by photomolding.
[0088] <14B> A dental product comprising a cured product of the photocurable composition according to any one of <1B> to <13B>.
[0089] <15B> The dental product according to <14B>, which is a dental cap or a lining material.
[0090] Effects of the Invention
[0091] According to the first embodiment of the present disclosure, it is possible to provide a photocurable composition that can obtain a cured product that has suppressed generation of cracks and fissures and is excellent in workability, and a dental product having the cured product of the photocurable composition.
[0092] According to the second embodiment of the present disclosure, a photocurable composition capable of obtaining a cured product having excellent handleability and suppressing discomfort when applied to a human body, and a dental product having the cured product of the photocurable composition can be provided. BRIEF DESCRIPTION OF THE DRAWINGS
[0093] [ Figure 1 ] is a diagram showing the appearance of a maxillary mouthguard according to one embodiment of the present disclosure.
[0094] [ Figure 2 ] is a diagram showing the thickness of the upper jaw mouthguard on the occlusal surface (flat type) of the central incisor.
[0095] [ Figure 3 ] is a diagram showing the thickness of the upper jaw mouthguard on the occlusal surface (non-planar type) of the central incisor.
[0096] [ Figure 4 ] is a diagram showing the thickness of the upper jaw mouthguard of the occlusal surface (flat type) of the second molar portion.
[0097] [ Figure 5 ] is a diagram showing the thickness of the upper jaw mouthguard of the occlusal surface (non-planar type) of the second molar portion. DETAILED DESCRIPTION
[0098] In the present disclosure, a numerical range expressed using "to" means a range including the numerical values described before and after "to" as the lower limit and the upper limit.
[0099] In addition, in this disclosure, "(meth)acrylic-based monomer" is a concept including both acrylic-based monomers and methacrylic-based monomers.
[0100] In addition, in this disclosure, "(meth)acryloyloxy group" is a concept including both acryloyloxy group and methacryloyloxy group, and when "acryloyloxy group" or "methacryloyloxy group" is described, it refers to only the group, respectively.
[0101] In the present disclosure, a "urethane bond" refers to a -NHC(=O)O- bond.
[0102] In the present disclosure, when referring to the amount of each component in a composition, if there are multiple substances corresponding to each component in the composition, unless otherwise specified, it means the total amount of the multiple substances present in the composition.
[0103] As the photocurable composition of the present disclosure, the following first embodiment and second embodiment can be mentioned.
[0104] <<Photocurable composition of the first embodiment>>
[0105] As the photocurable composition of the first embodiment, the following aspects 1a, 1b, and 1c can be mentioned.
[0106] Each form (for example, form 1a) may satisfy the characteristics of other forms (for example, form 1b and / or form 1c).
[0107] Method 1a
[0108] The photocurable composition of aspect 1a of the first embodiment includes a (meth)acrylic monomer component and a photopolymerization initiator, and the adhesive force of the cured product is 1.5 N or less, and the elongation at break of the cured product is 20% or more.
[0109] The inventors of the present disclosure have focused on improving the elongation at break of a cured product (hereinafter also simply referred to as a cured product) obtained by photocuring a photocurable composition in order to suppress the occurrence of cracks and fissures in a product.
[0110] The inventors of the present disclosure have studied the above aspects and have found that when the elongation at break of a cured product obtained by photocuring a photocurable composition (hereinafter also referred to as a cured product) is increased, the adhesive force of the cured product increases, which is one of the factors that reduce workability.
[0111] That is, from the viewpoint of obtaining a cured product that can achieve both suppression of cracks and fissures and handleability, it is important to increase the elongation at break of a cured product obtained by photocuring a photocurable composition and suppress the adhesive force of the cured product.
[0112] The photocurable composition of embodiment 1a comprises a (meth) acrylic acid monomer component and a photopolymerization initiator, and the adhesion of the cured product is 1.5N or less, and the elongation at break of the cured product is 20% or more, so that when the photocurable composition of the first embodiment is photocured, a cured product having excellent elongation at break and suppressed adhesion can be obtained. Thus, a cured product having suppressed cracking and fissures and excellent workability can be obtained.
[0113] <Adhesion of cured product>
[0114] The adhesive force of the cured product obtained by photocuring the photocurable composition of embodiment 1a is 1.5N or less.
[0115] Thereby, the handleability of the cured product can be improved.
[0116] From the same viewpoint as above, the adhesive force is preferably 1.0 N or less, more preferably 0.7 N or less, and further preferably 0.35 N or less.
[0117] The lower limit of the adhesive force of the cured product is not particularly limited, but may be greater than 0 N, and may be 0.01 N or more.
[0118] The adhesive force of the cured product was measured as follows.
[0119] First, the photocurable composition was irradiated with visible light using a 3D printer, thereby molding the photocurable composition into a shape of 20 mm in length × 20 mm in width × 2 mm in thickness to obtain a molded object (stacked width 50 μm). In the above-mentioned irradiation with visible light using the 3D printer, for each layer, the intensity of the visible light was 5.0 mJ / cm 2 ~10mJ / cm 2 The film is irradiated with visible light having a wavelength of 405 nm in a range of .
[0120] For the above-obtained shaped object, the 2 The molded object was irradiated with ultraviolet light having a wavelength of 365 nm under the conditions of , and the molded object was cured to obtain a cured object. The obtained cured object was used as the object for measuring the adhesive force.
[0121] The solidified object to be measured is pasted on the sample table, and an aluminum probe with a contact area of 10 mm in the vertical direction and 10 mm in the horizontal direction is in contact with the surface of the solidified object with a contact load of 0.98 ± 0.01 N / cm 2 Hold for 1.0±0.1 seconds.
[0122] Then, the probe was peeled off from the contact surface in a vertical direction at a speed of 5 mm per second using a tensile tester. Then, the maximum load required to peel off the probe from the contact surface was determined and defined as the adhesive force (unit: N) of the cured product of the present disclosure.
[0123] <Elongation at break of cured product>
[0124] Regarding the photocurable composition of embodiment 1a, the elongation at break of a cured product obtained by curing the photocurable composition is 20% or more.
[0125] This can suppress the occurrence of cracks (cracks, breaks, splits, etc.) when an external force is applied to the cured product.
[0126] In addition, by having the elongation at break of the cured product within the above range, the recovery property can be improved (increasing the recovery speed, suppressing the deformation during recovery, etc.), and the recovery property is the performance that the shape of the cured product is restored to the shape before the external force is applied when the external force is removed after the external force is temporarily applied to the cured product. In addition, when the elongation at break of the cured product is within the above range and the adhesion of the cured product is less than 1.5N, the above recovery property can be further improved. Further, when the elongation at break of the cured product is within the above range and the adhesion of the cured product is less than 1.5N, the deformation during recovery can be more effectively suppressed.
[0127] From the above viewpoints, the elongation at break of the cured product is preferably 40% or more, more preferably 60% or more.
[0128] The upper limit of the elongation at break may be 110% or less, 100% or less, or 90% or less.
[0129] In addition, in this disclosure, the elongation at break of a cured product is measured by the following method.
[0130] First, the photocurable composition was irradiated with visible light using a 3D printer to shape the photocurable composition into a dumbbell-shaped test piece conforming to ISO 37-2 to obtain a molded object (laminated width 50 μm).
[0131] In the above-mentioned irradiation of visible light using a 3D printer, for each layer, the irradiation rate was 5.0 mJ / cm 2 ~10mJ / cm 2 The film is irradiated with visible light having a wavelength of 405 nm under conditions in which the film has a desired thickness within a range of .
[0132] For the above-obtained shaped object, at 10 J / cm 2The molded object was irradiated with ultraviolet light having a wavelength of 365 nm under the conditions of , thereby obtaining a cured product. The obtained cured product was used as the object for measuring the elongation at break.
[0133] The elongation at break of the cured product to be measured was measured using a tensile tester at a tensile speed of 500±50 mm / min in accordance with ISO 37:2017.
[0134] (Hardness of cured product (Shore A hardness))
[0135] The hardness of the cured product of embodiment 1a is preferably 50 or more.
[0136] Generally, there is a tendency that the adhesive force of a cured product with a lower hardness (that is, a softer) is more likely to increase, and when the hardness of the cured product is 50 or more, the adhesive force of the cured product can be more effectively suppressed.
[0137] The upper limit of the hardness of the cured product is not particularly limited, but may be 99 or less.
[0138] In addition, as described above, there is generally a tendency for the adhesion to increase more easily as the hardness of the cured product is lower (i.e., softer). However, when the photocurable composition of the first embodiment is used, the adhesion of the cured product can be suppressed even if the hardness of the obtained cured product is 90 or less, and the adhesion of the cured product can be suppressed even if the hardness is 80 or less.
[0139] In addition, in this disclosure, the hardness of a cured product is measured by the following method.
[0140] First, the photocurable composition was irradiated with visible light using a 3D printer, thereby molding the photocurable composition into a shape of 25 mm in length × 25 mm in width × 6 mm in thickness to obtain a molded object (layer width 50 μm). In the above-mentioned irradiation with visible light using a 3D printer, for each layer, the irradiation rate was 5.0 mJ / cm 2 ~10mJ / cm 2 The film is irradiated with visible light having a wavelength of 405 nm under conditions in which the film has a desired thickness within a range of .
[0141] For the above-obtained shaped object, at 10 J / cm 2 The molded object was irradiated with ultraviolet light having a wavelength of 365 nm under the conditions of , thereby obtaining a cured product. The obtained cured product was used as the object of hardness measurement.
[0142] The hardness of the cured product was measured in accordance with ISO 7619-1:2010.
[0143] (Viscosity)
[0144] For the photocurable composition of embodiment 1a, from the viewpoint of suitability for producing dental products by photomolding, the viscosity measured at 25°C and 50 rpm (revolutions per minute) using an E-type viscometer is preferably 10 mPa·s to 5000 mPa·s, more preferably 20 mPa·s to 3000 mPa·s. The lower limit of the above viscosity is more preferably 50 mPa·s. The upper limit of the above viscosity is more preferably 2000 mPa·s, further preferably 1500 mPa·s, and particularly preferably 1200 mPa·s.
[0145] Method 1b
[0146] The photocurable composition of aspect 1b comprises a (meth)acrylic monomer component and a photopolymerization initiator, and the adhesive force of the cured product is 1.5 N or less, and the impact absorption of the cured product is 20% or more and 80% or less.
[0147] From the viewpoint of suppressing the occurrence of cracks and splits in products, the inventors of the present disclosure paid attention to the impact absorption of a cured product (hereinafter, also simply referred to as a cured product) obtained by photocuring a photocurable composition.
[0148] The inventors of the present disclosure have studied the above-mentioned points and have found that when the impact absorbency of a cured product is improved, the adhesive strength of the cured product increases, which is one of the factors that degrades the workability.
[0149] The photocurable composition of method 1b contains a (meth)acrylic monomer component and a photopolymerization initiator, the adhesion of the cured product is less than 1.5N, and the impact absorption of the cured product is more than 20% and less than 80%. Therefore, when the photocurable composition of the first embodiment is photocured, a cured product with suppressed cracking and fissures and excellent operability can be obtained.
[0150] In the embodiment 1b, the adhesive force of the cured product is the same as in the above embodiment 1a, and the preferred form is also the same.
[0151] <Shock Absorption>
[0152] The impact absorbency of the cured product of embodiment 1b is 20% to 80%.
[0153] When the impact absorbency of the cured product is 20% or more, the occurrence of cracks (occurrence of cracks, occurrence of breaks, occurrence of splits, etc.) in the cured product can be suppressed.
[0154] From the same viewpoint as above, the impact absorbency of the cured product is preferably 30% or more, more preferably 40% or more.
[0155] When the impact absorbency of the cured product is 80% or less, the adhesive force of the cured product can be prevented from becoming too large, thereby maintaining the handleability.
[0156] From the same viewpoint as above, the impact absorbency of the cured product is preferably 70% or less, more preferably 60% or less.
[0157] When the impact absorbency of the cured product is within the above range and the adhesive strength of the cured product is 1.5 N or less, the recovery property can be improved similarly to the above-mentioned elongation at break, and the deformation amount during recovery can be more preferably suppressed.
[0158] Examples of methods for adjusting the impact absorbency include a method for adjusting the impact absorbency by adjusting the aromatic ring concentration of the (meth)acrylic monomer component, a method for adjusting the impact absorbency by adjusting the (meth)acryloyl group concentration (mol / g) of the (meth)acrylic monomer (A) described later, etc. Details are described later.
[0159] -Measurement method of shock absorption-
[0160] The method for measuring the impact absorption of the cured product of the present disclosure is as follows.
[0161] First, the photocurable composition was irradiated with visible light using a 3D printer, thereby molding the photocurable composition into a shape of 20 mm in length × 20 mm in width × 3 mm in thickness to obtain a molded object (layer width 50 μm). In the above-mentioned irradiation with visible light using a 3D printer, for each layer, the irradiation rate was 5.0 mJ / cm 2 ~10mJ / cm 2 The film is irradiated with visible light having a wavelength of 405 nm under conditions in which the film has a desired thickness within a range of .
[0162] For the above-obtained shaped object, at 10 J / cm 2 The molded object was irradiated with ultraviolet light having a wavelength of 365 nm under the conditions of , and the molded object was cured to obtain a cured product. The obtained cured product was kept at 37° C. for 15 minutes and used as a subject for measuring impact absorption.
[0163] The impact absorption of the cured product of the present disclosure means the degree of reduction in the maximum load measured by a load cell when an iron ball is allowed to freely fall onto the cured product.
[0164] More specifically, the value of A calculated from the following formula is defined as the impact absorbency (A, unit: %) of the cured product of the present disclosure.
[0165] [Number 1]
[0166]
[0167] In the above formula, A (%) represents the impact absorption,
[0168] N0 represents the maximum load measured by the force sensor when a 1mm thick, 30mm long x 30mm wide zirconium oxide plate is placed on the force sensor at 23°C and an iron ball (16.7mm in diameter, 18.8g) is freely dropped from a position 50cm above the zirconium oxide plate to the center of the plate.
[0169] N represents: at 23°C, a zirconia plate with a thickness of 1mm, and a length of 30mm×width of 30mm is placed on the force sensor, and a solidified object of measurement with a thickness of 3mm, a length of 20mm, and a width of 20mm is placed in the center of the above zirconia plate. In this state, an iron ball (diameter 16.7mm, 18.8g) is allowed to freely fall from a position 50cm above the force sensor above the solidified object to the center of the solidified object, and this is the maximum load measured by the force sensor.
[0170] Method 1c
[0171] The photocurable composition of mode 1c of the first embodiment comprises a (meth)acrylic monomer component and a photopolymerization initiator, wherein the (meth)acrylic monomer component comprises a (meth)acrylic monomer (A) having two (meth)acryloyl groups and a (meth)acrylic monomer (B) having one (meth)acryloyl group, wherein the molecular weight of the (meth)acrylic monomer (A) per one (meth)acryloyl group is greater than 300 g / mol, and at least one of the (meth)acrylic monomer (A) and the (meth)acrylic monomer (B) has an aromatic group.
[0172] Hereinafter, each component contained in the photocurable composition in the aspect 1a, the aspect 1b, and the aspect 1c of the first embodiment will be described in detail.
[0173] <(Meth)acrylic acid monomer component>
[0174] The photocurable composition of the first embodiment contains a (meth)acrylic monomer component.
[0175] Thereby, the elongation at break of the obtained cured product can be improved.
[0176] As the (meth)acrylic acid-based monomer component, any (meth)acrylic acid-based monomer may be used without particular limitation as long as it contains the (meth)acrylic acid-based monomer.
[0177] Among the above, from the viewpoint of obtaining a cured product having excellent elongation at break and suppressed adhesive force, the (meth)acrylic monomer component preferably contains a (meth)acrylic monomer (A) having two (meth)acryloyl groups and a (meth)acrylic monomer (B) having one (meth)acryloyl group.
[0178] In the photocurable composition of the first embodiment, the (meth)acrylic monomer component preferably has an aromatic group.
[0179] The (meth)acrylic monomer component in the first embodiment contains an acryloyl group. Generally, since the acryloyl group has hydrophilic properties, when a cured product is produced using a photocurable composition containing a (meth)acrylic monomer, the adhesive strength of the cured product tends to increase.
[0180] However, when the (meth)acrylic monomer component has an aromatic group, the adhesive force of the obtained cured product can be well suppressed due to the hydrophobicity of the aromatic group itself and the π-π interaction between the aromatic groups.
[0181] As a result, the photocurable composition of the first embodiment can more satisfactorily suppress the adhesive strength of the cured product even when a (meth)acrylic monomer containing an acryloyl group that may increase the adhesive strength of the cured product is used.
[0182] In general, when the hygroscopicity of a cured product is high, cracks are likely to occur at the locations of the cured product that have absorbed moisture.
[0183] As for the above, since aromatic groups have high hydrophobicity, the use of a (meth)acrylic monomer having an aromatic group in the photocurable composition of the first embodiment can reduce the hygroscopicity of the obtained cured product and improve the elongation at break of the cured product.
[0184] Furthermore, the impact absorbency can be improved by increasing the aromatic ring concentration, and the impact absorbency can be reduced by suppressing the aromatic ring concentration.
[0185] From the above viewpoints, the aromatic ring concentration in the (meth)acrylic monomer component is preferably 0.00100 mol / g or more, more preferably 0.00250 mol / g or more, and even more preferably 0.00450 mol / g or more.
[0186] The upper limit of the aromatic ring concentration in the (meth)acrylic monomer component is preferably 0.010 mol / g or less, and more preferably 0.008 mol / g or less, from the viewpoint of suppressing yellowing of the cured product.
[0187] Examples of the aromatic group include phenyl, phenylene, naphthyl, and anthracenyl.
[0188] Among the above, as the aromatic group, a phenyl group and a phenylene group are preferred.
[0189] ((Meth)acrylic monomer (A) having two (meth)acryloyl groups)
[0190] The (meth)acrylic monomer component in the first embodiment preferably contains a (meth)acrylic monomer (A) having two (meth)acryloyl groups.
[0191] The (meth)acrylic monomer (A) does not have a (meth)acryloyl group other than two (meth)acryloyl groups.
[0192] As for the (meth)acrylic monomer (A), as long as it is a (meth)acrylic monomer having two (meth)acryloyl groups, one kind may be used, or two or more kinds may be used.
[0193] The (meth)acrylic monomer (A) is preferably a (meth)acrylic monomer having two (meth)acryloyloxy groups.
[0194] The (meth)acrylic monomer (A) preferably contains a urethane bond, whereby the elongation at break of the obtained cured product can be increased.
[0195] The number of urethane bonds contained in the (meth)acrylic monomer (A) is preferably 1 to 5, more preferably 2 to 4, and even more preferably 2, from the viewpoint of the elongation at break and adhesive strength of the obtained cured product.
[0196] By increasing the (meth)acryloyl equivalent of the (meth)acrylic monomer (A) (that is, increasing the molecular weight of the (meth)acrylic monomer (A)), the impact absorption can be improved, and by decreasing the (meth)acryloyl equivalent, the impact absorption can be reduced.
[0197] That is, the impact absorbency can be improved by reducing the (meth)acryloyl group concentration (mol / g) of the (meth)acrylic monomer (A), and the impact absorbency can be reduced by increasing the (meth)acryloyl group concentration (mol / g) of the (meth)acrylic monomer (A).
[0198] From the above viewpoints and from the viewpoint of increasing the hardness of the obtained cured product, the (meth)acryloyl group concentration (mol / g) in the (meth)acrylic monomer (A) is preferably 0.001 mol / g to 0.01 mol / g, more preferably 0.001 mol / g to 0.005 mol / g.
[0199] The (meth)acrylic monomer (A) preferably contains a compound represented by the following formula (1).
[0200] Furthermore, the (meth)acrylic monomer (A) is also preferably a compound represented by the following formula (1).
[0201] [Chemistry 3]
[0202]
[0203] In formula (1), R 1 and R 2 Each independently represents a divalent linking group, R 3 Each is independently a methyl group or a hydrogen atom.
[0204] In the above formula (1), R 1 It is preferably a divalent organic group, and more preferably a divalent organic group which may have one or more selected from the group consisting of an aromatic structure, an alicyclic structure, an ether bond, an ester bond, and a urethane bond.
[0205] R in formula (1) 1 In the above, the divalent organic group preferably includes a divalent chain hydrocarbon group,
[0206] More preferably, it contains a divalent chain hydrocarbon group and at least one group selected from the group consisting of a divalent hydrocarbon group having a cyclic structure and a divalent group containing a heteroatom.
[0207] Examples of the cyclic structure include an aromatic structure and an alicyclic structure.
[0208] The divalent chain hydrocarbon group may be saturated or unsaturated, and may have a substituent. The divalent chain hydrocarbon group may be a linear or branched alkylene group.
[0209] From the viewpoint of suppressing the viscosity of the photocurable composition, improving the elongation at break of the obtained cured product, and suppressing the adhesive force of the obtained cured product, R in formula (1) 1 It preferably contains an oxyalkylene structure or a polyester structure.
[0210] In addition, from the same viewpoint as above, R in formula (1) 1 It is preferably a divalent chain hydrocarbon group having no substituent.
[0211] R in formula (1) 1 In the formula (A), the number of carbon atoms in the divalent organic group may be, for example, in the range of 5 to 2,500, and preferably in the range of 5 to 2,000.
[0212] R in formula (1) 1 In the above, the divalent organic group may contain a hetero atom. Examples of the hetero atom include an oxygen atom and a nitrogen atom.
[0213] R in formula (1) 1 In the examples of the divalent hydrocarbon group having an aromatic structure, an arylene group, an alkylenearylene group, an alkylenearylenealkylene group, and an arylenealkylenearylene group may be mentioned.
[0214] R in formula (1) 1 In the example of the divalent hydrocarbon group having an alicyclic structure, for example, a cyclopropylene group, a cyclobutylene group, a cyclopentylene group, a cyclohexylene group, a cyclohexenylene group, a cycloheptylene group, a cyclooctylene group, a cyclononylene group, a cyclodecylene group, a cycloundecylene group, a cyclododecylene group, a cyclotridecylene group, a cyclotetradecylene group, a cyclopentadecylene group, a cyclooctadecylene group, a cycloeicosylene group, a bicyclohexylene group, a norbornylene group, an isobornylene group, and an adamantylene group.
[0215] R in formula (1) 1 It may have a substituent, and examples of the substituent include a linear or branched alkyl group having 1 to 6 carbon atoms.
[0216] In formula (1), from the viewpoint of recovery and impact absorption, R 1 It is preferably a divalent chain hydrocarbon group, or a group consisting of a divalent chain hydrocarbon group and at least one group selected from the group consisting of a divalent hydrocarbon group having an alicyclic structure, a divalent hydrocarbon group having an aromatic structure, and a divalent group containing a heteroatom,
[0217] R 1 More preferably, it is a divalent chain hydrocarbon group, or a group consisting of a divalent chain hydrocarbon group and at least one group selected from the group consisting of a divalent hydrocarbon group having an alicyclic structure and a divalent group containing a heteroatom.
[0218] From the viewpoint of restorability and impact absorption, the divalent hydrocarbon group having an aromatic structure is preferably a divalent hydrocarbon group represented by the following formula (1-a).
[0219] Furthermore, from the viewpoint of suppressing yellowing of the cured product and improving weather resistance, the divalent hydrocarbon group having an aromatic structure is preferably a divalent hydrocarbon group represented by the following formula (1-a).
[0220] [Chemistry 4]
[0221]
[0222] (In formula (1-a), * indicates a binding position.)
[0223] From the perspective of resilience and shock absorption, R 1 The heteroatom-containing divalent group in preferably includes at least one bond selected from the group consisting of a urethane bond and an ether bond.
[0224] In the above formula (1), preferably R 2 Each independently represents a divalent chain hydrocarbon group which may have a substituent.
[0225] Suitable as R 2 The divalent chain hydrocarbon group suitable as R 1 The same is true for the divalent chain hydrocarbon groups. 2 The divalent chain hydrocarbon group of R preferably has 2 to 6 carbon atoms, and more preferably has 2 to 3 carbon atoms. 2 The divalent chain hydrocarbon group is preferably an unsubstituted divalent chain hydrocarbon group having 2 to 6 carbon atoms, and more preferably has 2 to 3 carbon atoms.
[0226] In R 2 When there is a substituent, examples of the substituent include alkyl groups having 1 to 6 carbon atoms such as methyl and ethyl; aryl groups; cycloalkyl groups having 3 to 6 carbon atoms such as cyclopentyl and cyclohexyl; tolyl: xylyl: cumyl; styryl: alkoxyphenyl groups such as methoxyphenyl, ethoxyphenyl and propoxyphenyl.
[0227] As the molecular weight of the (meth)acrylic monomer (A), the weight average molecular weight is preferably 600 to 30,000, more preferably 800 to 20,000, and further preferably 1,000 to 5,000.
[0228] The aromatic ring concentration in the (meth)acrylic monomer (A) is preferably 0.0020 mol / g or less, and more preferably 0.0016 mol / g or less, from the viewpoint of recovery and impact absorption.
[0229] The aromatic ring concentration in the (meth)acrylic monomer (A) may be, for example, 0.0010 mol / g or more.
[0230] (Molecular weight per (meth)acryloyl group)
[0231] The molecular weight of the (meth)acrylic monomer (A) per (meth)acryloyl group is preferably 300 g / mol or more.
[0232] This can further improve the elongation at break of the cured product.
[0233] From the same viewpoint as described above, the molecular weight of the (meth)acrylic monomer (A) per (meth)acryloyl group is more preferably 600 g / mol or more.
[0234] The molecular weight of the (meth)acrylic monomer (A) per (meth)acryloyl group is preferably 15,000 g / mol or less, more preferably 10,000 g / mol or less, and even more preferably 2,000 g / mol or less.
[0235] The molecular weight of the (meth)acrylic monomer (A) per (meth)acryloyl group is preferably 50 to 15,000 g / mol, more preferably 150 to 10,000 g / mol, and further preferably 250 to 2,000 g / mol.
[0236] In addition, when a plurality of (meth)acrylic monomers are contained as the (meth)acrylic monomer (A), the molecular weight per one (meth)acryloyl group is calculated as the mass average value of the molecular weights of the respective (meth)acrylic monomers.
[0237] ((Meth)acrylic monomer (B) having one (meth)acryloyl group)
[0238] The (meth)acrylic monomer component in the first embodiment preferably contains a (meth)acrylic monomer (B) having one (meth)acrylic group. The (meth)acrylic monomer (B) does not have a (meth)acrylic group other than the one (meth)acrylic group.
[0239] As the (meth)acrylic monomer (B), as long as it is an acrylic monomer having one (meth)acryloyl group, one kind may be used or two or more kinds may be used.
[0240] The (meth)acrylic monomer (B) preferably contains a ring structure. This can increase the hardness of the obtained cured product and suppress the adhesive force of the obtained cured product.
[0241] The ring structure is preferably an aromatic structure or an alicyclic structure, and more preferably an aromatic structure.
[0242] When the (meth)acrylic monomer (B) contains an aromatic structure, the number of aromatic rings contained in the (meth)acrylic monomer (B) is preferably 1 to 4, more preferably 2 and 3.
[0243] The (meth)acrylic monomer (B) is preferably a compound represented by the following formula (2) or (3), and more preferably a compound represented by the following formula (2).
[0244] [Chemistry 5]
[0245]
[0246] In formula (2), R 6It is a monovalent organic group which may have a ring structure.
[0247] In formula (3), R 7 and R 8 are each independently a monovalent organic group which may have a ring structure, or a hydrogen atom, R 7 With R 8 Can combine with each other to form a ring.
[0248] The (meth)acrylic monomer (B) is preferably a compound represented by formula (2), wherein R 6 It is preferably a monovalent organic group having 3 to 30 carbon atoms and having a ring structure (preferably an aromatic ring structure), and more preferably a monovalent organic group having 6 to 20 carbon atoms and having a ring structure (preferably an aromatic ring structure).
[0249] In formula (2), R 6 The structure may be represented by the following formula (4).
[0250] *-L1-A (4)
[0251] In formula (4), L1 is a single bond or a divalent chain hydrocarbon group having 1 to 30 carbon atoms which may have a hetero atom O or N, and A is a hydrogen atom, a monovalent alicyclic group having 3 to 30 carbon atoms which may have a hetero atom O or N, or an aryl group having 6 to 30 carbon atoms. * indicates a bonding position.
[0252] In the formula (4), the divalent chain hydrocarbon group having 1 to 30 carbon atoms and optionally having a hetero atom O or N represented by L1 may be linear or branched.
[0253] L1 preferably has 1 to 20 carbon atoms, more preferably 1 to 10 carbon atoms, and even more preferably 1 to 8 carbon atoms.
[0254] When L1 contains a hetero atom, the number of the hetero atoms is preferably 1 to 6, and more preferably 1 or 2.
[0255] L1 may have a substituent. Suitable examples of the substituent of L1 include an alkyl group having 1 to 3 carbon atoms, a hydroxyl group, and an alkyl group having 1 to 3 carbon atoms in which one or two hydrogen atoms are substituted with a hydroxyl group.
[0256] L1 may include a urethane bond. When L1 includes a urethane bond, the number of urethane bonds may be 1 or 2.
[0257] In the formula (4), examples of the monovalent alicyclic group having 3 to 20 carbon atoms which may have a hetero atom O or N and which is represented by A include cyclopropyl, cyclobutyl, cyclopentyl, cyclohexyl, cyclohexenyl, cycloheptyl, cyclooctyl, cyclononyl, cyclodecyl, cycloundecyl, cyclododecyl, cyclotridecyl, cyclotetradecyl, cyclopentadecyl, cyclooctadecyl, cycloeicosyl, bicyclohexyl, norbornyl, isobornyl, adamantyl, morpholinyl, piperidinyl, piperazinyl, dicyclohexyl, isobornyl, ... The monovalent alicyclic group preferably has 5 to 12 carbon atoms, more preferably 6 to 10 carbon atoms.
[0258] In the formula (4), examples of the aromatic structure represented by A include a phenyl structure, a biphenyl structure, a naphthyl structure, and an anthracenyl structure.
[0259] A may have a substituent. Suitable examples of the substituent of A include alkyl groups having 1 to 6 carbon atoms such as methyl and ethyl; hydroxyl groups; alkyl groups having 1 to 6 carbon atoms in which one or two hydrogen atoms are replaced by hydroxyl groups; aryl groups; cycloalkyl groups having 3 to 6 carbon atoms such as cyclopentyl and cyclohexyl groups; tolyl groups: xylyl groups: cumyl groups; styryl groups: alkoxyphenyl groups such as methoxyphenyl, ethoxyphenyl and propoxyphenyl groups.
[0260] In formula (2), the total number of carbon atoms of -L1-A is preferably 1-30, more preferably 1-20.
[0261] In formula (3), R 7 and R 8 are each independently a monovalent organic group which may have a ring structure, or a hydrogen atom, R 7 With R 8 Can combine with each other to form a ring.
[0262] As a suitable R 7 and R 8 , and examples thereof include monovalent hydrocarbon groups having 1 to 30 carbon atoms which may have a hetero atom O or N. The hydrocarbon group may be linear or branched, saturated or unsaturated, and may have a substituent.
[0263] As R 7 and R 8 , preferably has 1 to 20 carbon atoms, more preferably 1 to 10 carbon atoms.
[0264] As R 7 and R 8 Examples of the organic group in include alkyl groups having 1 to 30 carbon atoms, such as methyl, ethyl, and propyl groups, which may have heteroatoms O or N. Among the above, R is preferably 7 and R 8One of them is a hydroxyethyl group or a butoxymethyl group, and the other is a hydrogen atom.
[0265] In R 7 and R 8 When any one of them is a hydroxyethyl group or a butoxymethyl group and the other is a hydrogen atom, examples of the (meth)acrylic monomer (B) include the following monomers.
[0266] As R 7 With R 8 Examples of the (meth)acrylic monomer (B) when they are bonded to each other to form a ring include the following monomers.
[0267] [Chemistry 6]
[0268]
[0269] The molecular weight of the (meth)acrylic monomer (B) is not particularly limited, but the weight average molecular weight is preferably 80 to 500, more preferably 100 to 400, and even more preferably 130 to 320.
[0270] Examples of compounds suitable as the (meth)acrylic monomer (B) include compounds used in Examples described below.
[0271] In the photocurable composition of the first embodiment, it is preferred that at least one of the (meth)acrylic monomer (A) and the (meth)acrylic monomer (B) has a ring structure.
[0272] Thereby, the elongation at break of the obtained cured product can be further increased, and the adhesive force of the obtained cured product can be suppressed.
[0273] Examples of the ring structure include an aromatic group and an alicyclic group.
[0274] In the photocurable composition of the first embodiment, it is preferred that at least one of the (meth)acrylic monomer (A) and the (meth)acrylic monomer (B) has an aromatic group.
[0275] As described above, when at least one of the (meth)acrylic monomer (A) and the (meth)acrylic monomer (B) has an aromatic group, the adhesive force of the obtained cured product can be well suppressed.
[0276] Furthermore, by using a (meth)acrylic monomer having an aromatic group in the photocurable composition of the first embodiment, the hygroscopicity of the obtained cured product can be reduced, and the elongation at break of the cured product can be improved favorably.
[0277] In the photocurable composition of the first embodiment, the content of the (meth)acrylic monomer (A) is preferably 250 to 800 parts by mass, more preferably 350 to 650 parts by mass, and even more preferably 380 to 500 parts by mass, relative to 1000 parts by mass of the total content of the (meth)acrylic monomer (A) and the (meth)acrylic monomer (B).
[0278] In the photocurable composition of the first embodiment, the total content of the (meth)acrylic monomer (A) and the (meth)acrylic monomer (B) in the (meth)acrylic monomer component is preferably 90% by mass or more, more preferably 95% by mass or more.
[0279] The photocurable composition of the first embodiment may include acrylic rubber particles. When the photocurable composition of the first embodiment includes acrylic rubber particles, the content of acrylic rubber particles in the photocurable composition of the first embodiment is preferably 0.1% by mass to 30% by mass. In addition, when the photocurable composition of the first embodiment includes acrylic rubber particles, the total content of the (meth) acrylic monomer (A), the (meth) acrylic monomer (B) and the acrylic rubber particles in the (meth) acrylic monomer component is preferably 90% by mass or more, more preferably 95% by mass or more.
[0280] Regarding the (meth)acrylic monomer (A) and the (meth)acrylic monomer (B) in the first embodiment, from the viewpoint of being able to increase the tensile elongation of the cured product and reduce the adhesive force, Z in the following formula α calculated using the molecular weight (g / mol) of the (meth)acrylic monomer (A) per (meth)acrylic group [i.e., molecular weight of the (meth)acrylic monomer (A) / number of (meth)acrylic groups in the (meth)acrylic monomer (A)] and the aromatic ring concentration (mol / g) in the (meth)acrylic monomer component is preferably greater than 0, more preferably 0.00100 to 100, and even more preferably 0.200 to 50.
[0281] Z=X×Y Formula α
[0282] X (g / mol): (molecular weight of (meth)acrylic monomer (A) per (meth)acryloyl group) -200
[0283] Y (mol / g): (aromatic ring concentration in (meth)acrylic monomer component (mol / g) - 0.00100
[0284] In the first embodiment, the (meth)acrylic monomer (A) and the (meth)acrylic monomer (B) are preferably 5×10-6 in terms of increasing the tensile elongation of the cured product, reducing the adhesive force, and further improving the recovery property. The Z1 in the following formula β calculated using the molecular weight (g / mol) of the (meth)acrylic monomer (A) per (meth)acryloyl group and the aromatic ring concentration (mol / g) in the (meth)acrylic monomer component is preferably 5×10-6. 3 ~500×10 4 , more preferably 1×10 4 ~100×10 4 .
[0285] In addition, the upper limit of the numerical value in these ranges is also preferable from the viewpoint of improving the shapeability (for example, surface roughness, etc.).
[0286] The lower limits of the numerical values in these ranges are also preferred from the viewpoint of suppressing yellowing.
[0287] Z1=X1 / Y1 Formula β
[0288] X1 (g / mol): Molecular weight of the (meth)acrylic monomer (A) per (meth)acryloyl group
[0289] Y1 (mol / g): Aromatic ring concentration in the (meth)acrylic monomer component
[0290] The photocurable composition of the first embodiment preferably satisfies at least one of the following (a) and (b).
[0291] (a) The (meth)acrylic monomer (A) comprises a (meth)acrylic monomer (A-1) having a molecular weight of 300 g / mol to 600 g / mol per (meth)acryloyl group and a (meth)acrylic monomer (A-2) having a molecular weight of more than 600 g / mol to 15,000 g / mol per (meth)acryloyl group.
[0292] (b) The (meth)acrylic monomer (B) includes a (meth)acrylic monomer (B-1) having two aromatic rings and a (meth)acrylic monomer (B-2) having one aromatic ring.
[0293] The photocurable composition of the first embodiment satisfies at least one of (a) and (b), so that the balance among adhesive force, elongation at break, and impact resistance is improved, and the recovery property is improved.
[0294] Examples of the (meth)acrylic monomer (A-1) having a molecular weight of 300 g / mol to 600 g / mol per (meth)acryloyl group include AH-600 (manufactured by Kyoeisha Chemical Co., Ltd.) and MMD-352 described below.
[0295] Examples of the (meth)acrylic monomer (A-2) having a molecular weight of more than 600 g / mol and less than 15,000 g / mol per (meth)acryloyl group include UA-160TM (manufactured by Shin-Nakamura Chemical Co., Ltd.), UA-122P (manufactured by Shin-Nakamura Chemical Co., Ltd.), UN-2700 (manufactured by Negami Industries Co., Ltd.), UN-2600 (manufactured by Negami Industries Co., Ltd.), UN-352 (manufactured by Negami Industries Co., Ltd.), Ebecryl 8402 (manufactured by Daicel Allnex Corporation), and Ebecryl 230 (manufactured by Daicel Allnex Corporation), which are described later.
[0296] The content of the (meth)acrylic monomer (A-1) is preferably 50 to 450 parts by mass, more preferably 80 to 350 parts by mass, and even more preferably 100 to 250 parts by mass, relative to 1000 parts by mass of the total content of the (meth)acrylic monomer (A) and the (meth)acrylic monomer (B).
[0297] The content of the (meth)acrylic monomer (A-2) is preferably 200 to 850 parts by mass, more preferably 220 to 650 parts by mass, and even more preferably 250 to 500 parts by mass, relative to 1000 parts by mass of the total content of the (meth)acrylic monomer (A) and the (meth)acrylic monomer (B).
[0298] It should be noted that, in the photocurable composition of the first embodiment, whether it is the case where only one of the (meth)acrylic monomer (A-1) and the (meth)acrylic monomer (A-2) is contained or the case where both are contained, the contents of the (meth)acrylic monomer (A-1) and the (meth)acrylic monomer (A-2) are preferably within the above range.
[0299] The ratio of the content of the (meth)acrylic monomer (A-1) to the total content of the (meth)acrylic monomer (A-1) and the (meth)acrylic monomer (A-2) is preferably 10% by mass to 70% by mass, more preferably 15% by mass to 50% by mass, and even more preferably 20% by mass to 40% by mass.
[0300] Examples of the (meth)acrylic monomer (B-1) having two aromatic rings include POBA (manufactured by Kyoeisha Chemical Co., Ltd.), HRD01 (manufactured by Nichijo Techno Fine Chemical Co., Ltd.), and M110 (manufactured by Toagosei Co., Ltd.).
[0301] Examples of the (meth)acrylic monomer (B-2) having one aromatic ring include PO-A (manufactured by Kyoeisha Chemical Co., Ltd.), M113 (manufactured by Toagosei Co., Ltd.), P2H-A (manufactured by Kyoeisha Chemical Co., Ltd.), BZ (manufactured by Kyoeisha Chemical Co., Ltd.), M-600A (manufactured by Kyoeisha Chemical Co., Ltd.), PO (manufactured by Kyoeisha Chemical Co., Ltd.), and M111 (manufactured by Toagosei Co., Ltd.).
[0302] The content of the (meth)acrylic monomer (B-1) is preferably 100 to 600 parts by mass, more preferably 150 to 500 parts by mass, and even more preferably 200 to 450 parts by mass, relative to 1000 parts by mass of the total content of the (meth)acrylic monomer (A) and the (meth)acrylic monomer (B).
[0303] The content of the (meth)acrylic monomer (B-2) is preferably 100 to 600 parts by mass, more preferably 150 to 500 parts by mass, and even more preferably 200 to 450 parts by mass, relative to 1000 parts by mass of the total content of the (meth)acrylic monomer (A) and the (meth)acrylic monomer (B).
[0304] It should be noted that, in the photocurable composition of the first embodiment, whether it is the case where only one of the (meth)acrylic monomer (B-1) and the (meth)acrylic monomer (B-2) is contained or the case where both are contained, the contents of the (meth)acrylic monomer (B-1) and the (meth)acrylic monomer (B-2) are preferably within the above range.
[0305] The content of the (meth)acrylic monomer (B-1) is preferably 20% to 80% by mass, more preferably 30% to 70% by mass, and even more preferably 40% to 60% by mass, relative to the total content of the (meth)acrylic monomer (B-1) and the (meth)acrylic monomer (B-2).
[0306] (Other additives in the (meth)acrylic acid monomer component)
[0307] The (meth)acrylic monomer component in the first embodiment may contain other additives in addition to the (meth)acrylic monomer (A) and the (meth)acrylic monomer (B).
[0308] As other additives, for example, a trifunctional (meth)acrylic monomer and the like are mentioned.
[0309] Among the above, trifunctional (meth)acrylic monomers can reduce the adhesive force of the cured product. On the other hand, trifunctional (meth)acrylic monomers may reduce the elongation at break of the cured product, so it is preferably added in a small amount within a range that can maintain the elongation at break.
[0310] (Photopolymerization Initiator)
[0311] The photocurable composition of the first embodiment contains a photopolymerization initiator.
[0312] The photopolymerization initiator is not particularly limited as long as it is a substance that generates radicals by light irradiation, but is preferably a photopolymerization initiator that generates radicals at the wavelength of light used in photomodeling.
[0313] The wavelength of light used in light shaping generally ranges from 365 nm to 500 nm, but is preferably from 365 nm to 430 nm, and more preferably from 365 nm to 420 nm in practical terms.
[0314] Examples of the photopolymerization initiator that generates free radicals at the wavelength of light used in photomodeling include alkylphenone compounds, acylphosphine oxide compounds, titanocene compounds, oxime ester compounds, benzoin compounds, acetophenone compounds, benzophenone compounds, thioxanthone compounds, α-acyloxime ester compounds, phenyl glyoxylate compounds, benzil compounds, azo compounds, diphenyl sulfide compounds, organic pigment compounds, iron-phthalocyanine compounds, benzoin ether compounds, and anthraquinone compounds.
[0315] Among them, alkylphenone compounds and acylphosphine oxide compounds are preferred from the viewpoint of reactivity and the like.
[0316] Examples of the alkylphenone-based compound include 1-hydroxy-cyclohexyl-phenyl-ketone (Omnirad 184: manufactured by IGM Resins).
[0317] Examples of the acylphosphine oxide-based compound include bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide (Omnirad 819: manufactured by IGMresins) and 2,4,6-trimethylbenzoyl-diphenylphosphine oxide (Omnirad TPO: manufactured by IGMresins).
[0318] The photocurable composition of the first embodiment may contain only one type of photopolymerization initiator, or may contain two or more types.
[0319] The content of the photopolymerization initiator in the photocurable composition of the first embodiment (the total content when two or more types are used) is preferably 0.1 to 10% by mass, more preferably 0.2 to 5% by mass, and even more preferably 0.3 to 3% by mass.
[0320] <Other ingredients>
[0321] The photocurable composition of the first embodiment may contain one or more other components other than the (meth)acrylic monomer (A), the (meth)acrylic monomer (B), and the photopolymerization initiator, as necessary.
[0322] When the photocurable composition contains the aforementioned other components, the total mass of the (meth)acrylic monomer (A), the (meth)acrylic monomer (B) and the photopolymerization initiator is preferably 30 mass % or more, more preferably 50 mass % or more, more preferably 70 mass % or more, further preferably 80 mass % or more, further preferably 90 mass % or more, particularly preferably 95 mass % or more, relative to the total mass of the photocurable composition.
[0323] As other components, for example, monomers other than the (meth)acrylic monomer (A) and the (meth)acrylic monomer (B) can be mentioned.
[0324] When the photocurable composition contains monomers other than the (meth)acrylic monomer (A) and the (meth)acrylic monomer (B) as other components, the content of the monomer as other components is preferably 50% by mass or less, more preferably 30% by mass or less, further preferably 20% by mass or less, and particularly preferably 10% by mass or less, relative to the total of the (meth)acrylic monomer (A) and the (meth)acrylic monomer (B).
[0325] Examples of other components include colorants, coupling agents such as silane coupling agents (eg, 3-acryloxypropyltrimethoxysilane), rubber agents, ion trapping agents, ion exchangers, leveling agents, plasticizers, additives such as defoaming agents, and thermal polymerization initiators.
[0326] When the photocurable composition of the first embodiment contains a thermal polymerization initiator, photocuring and thermal curing can be used in combination. Examples of the thermal polymerization initiator include a thermal radical generator and an amine compound.
[0327] The method for preparing the photocurable composition of the first embodiment is not particularly limited, and an example thereof includes mixing the (meth)acrylic monomer (A), the (meth)acrylic monomer (B), and a photopolymerization initiator (and other components as necessary).
[0328] The method for mixing the components is not particularly limited, and examples thereof include dissolution using ultrasonic waves, a double-arm mixer, a roll kneader, a twin-screw extruder, a ball mill kneader, a planetary mixer, and the like.
[0329] The photocurable composition of the present embodiment may be prepared by mixing the components, filtering with a filter to remove impurities, and further performing a vacuum degassing treatment.
[0330] "Solid Object"
[0331] There is no particular limitation on the method for photocuring using the photocurable composition of the first embodiment, and any known method and apparatus can be used. For example, the following method can be cited: by repeatedly performing the step of forming a thin film composed of the photocurable composition of the first embodiment and the step of irradiating the thin film with light to obtain a cured layer, the cured layer is laminated in multiple layers to produce a cured product of a desired shape. It should be noted that the obtained cured product can be used directly, or it can be further post-cured by light irradiation, heating, etc. to improve its mechanical properties, shape stability, etc. before use.
[0332] <Light Modeling>
[0333] The photocurable composition of the first embodiment is preferably used for photomodeling.
[0334] Among them, the photocurable composition of the first embodiment can be suitably used in a modeling method using a 3D printer.
[0335] In the present disclosure, “photomodeling” is one of the three-dimensional modeling methods using a 3D printer.
[0336] <3D Printer>
[0337] Examples of the light modeling method include an SLA (Stereo Lithography Apparatus) method, a DLP (Digital Light Processing) method, and an inkjet method.
[0338] The photocurable composition of the present embodiment is particularly suitable for SLA-based or DLP-based optical modeling.
[0339] As the SLA method, there is a method of obtaining a three-dimensional object by irradiating a photocurable composition with a dot-shaped ultraviolet laser.
[0340] When dental products and the like are produced by the SLA method, for example, the following lamination operation can be repeated: the photocurable composition of the present embodiment is stored in a container, the liquid surface of the photocurable composition is selectively irradiated with a point-shaped ultraviolet laser in a manner that a desired pattern can be obtained to cure the photocurable composition, a cured layer of a desired thickness is formed on a molding table, and then the molding table is lowered, and a layer of liquid photocurable composition is supplied on the cured layer, and cured in the same manner to obtain a continuous cured layer. In this way, dental products and the like can be produced.
[0341] As the DLP method, there is mentioned a method of obtaining a three-dimensional object by irradiating a photocurable composition with planar light.
[0342] Regarding the method of obtaining a three-dimensional object by the DLP method, for example, the descriptions of Japanese Patent No. 5111880 and Japanese Patent No. 5235056 can be appropriately referred to.
[0343] When a dental product or the like is produced by a DLP method, for example, a lamp emitting light other than laser light, such as a high-pressure mercury lamp, an ultra-high-pressure mercury lamp, a low-pressure mercury lamp, or an LED or the like can be used as a light source, and a planar drawing mask having a plurality of digital micro-mirror shutters arranged in a planar shape is arranged between the light source and the molding surface of the photocurable composition, and light is irradiated to the molding surface of the photocurable composition through the planar drawing mask to sequentially stack a cured layer having a predetermined shape pattern. In this way, a dental product or the like can be produced.
[0344] Examples of the inkjet method include a method in which droplets of a photocurable composition are continuously ejected from an inkjet nozzle onto a substrate, and the droplets attached to the substrate are irradiated with light to obtain a three-dimensional object.
[0345] When a dental product or the like is produced by an inkjet method, for example, a photocurable composition can be ejected from the inkjet nozzle onto a substrate while a nozzle head having an inkjet nozzle and a light source is scanned in a plane, and the ejected photocurable composition is irradiated with light to form a cured layer, and these operations are repeated to sequentially stack the cured layers. In this way, a dental product or the like can be produced.
[0346] Dental products
[0347] The photocurable composition of the first embodiment is suitable for producing a dental product by photomolding.
[0348] Furthermore, the photocurable composition of the first embodiment is suitable for producing a dental cap, a gum cover, or a lining material by photomolding, and is more suitable for producing a dental cap or a gum cover.
[0349] The dental product of the first embodiment preferably includes a cured product of the photocurable composition of the first embodiment.
[0350] The dental product as a cured product (i.e., a photo-shaped object) of the photocurable composition of the first embodiment is not particularly limited, and can be used in artificial teeth, restorations, medical instruments for use in the oral cavity, models (gum covers, etc.), etc., preferably instruments or models for use in the oral cavity, more preferably for braces (especially sports braces), gum covers or lining materials, and further preferably for braces (especially sports braces) or gum covers. It is preferred that the cured product of the photocurable composition of the first embodiment is used for at least a part of the dental product. As instruments for use in the oral cavity, for example, sports braces, mouth guards, braces for orthodontics, splints such as splints for occlusal adjustment or splints for treating temporomandibular joint disease, and braces for treating sleep apnea syndrome can be cited.
[0351] By using the cured product of the photocurable composition of the first embodiment, a medical device having excellent feel when used in the oral cavity and sufficient strength and hardness can be manufactured.
[0352] <Method for manufacturing a mouthguard and a mouthguard>
[0353] When the dental product of the first embodiment is a mouth guard, the mouth guard is preferably manufactured by photomolding.
[0354] The method for manufacturing a mouthguard of the first embodiment includes the step of creating three-dimensional image data of a mouthguard in which the thickness of the occlusal surface of the central incisor is 1.5 times or more the thickness of the occlusal surface of the second molar, and the mouthguard is preferably manufactured by photomodeling.
[0355] The mouthguard of the first embodiment is a light-molded object, and preferably the thickness of the occlusal surface of the central incisor portion is 1.5 times or more the thickness of the occlusal surface of the second molar portion.
[0356] In the past, the mouth guard was usually manufactured using a commercially available sheet material for a mouth guard and a blister molding machine. In this case, there is a tendency for the thickness of the occlusal surface of the mouth guard to become uniform, and the adjustment of the occlusal surface requires a lot of time. In addition, although the thickness can be adjusted by arranging multiple sheets at a specific location, it is difficult to set the manufacturing conditions of the mouth guard, which requires the operator's skills and a lot of time.
[0357] In a first embodiment, when a mouth guard is manufactured using a photocurable composition and a 3D printer, CAD design is performed by setting the thickness of the occlusal surface of the central incisor portion to be preferably 1.5 times but less than 5 times, and more preferably 2 times but less than 4 times, compared to the thickness of the occlusal surface of the second molar portion in the three-dimensional image data of the mouth guard, and the mouth guard is manufactured using a 3D printer through photomodeling, thereby eliminating the need to adjust the occlusal surface or simplifying the adjustment of the occlusal surface, which can significantly shorten the manufacturing time of the mouth guard.
[0358] The central incisor portion of the mouthguard refers to a portion of the mouthguard corresponding to the central incisor of the teeth, and is a portion of the mouthguard that contacts the central incisor when the mouthguard is worn.
[0359] The second molar portion of the mouthguard refers to a portion of the mouthguard corresponding to the second molar of the teeth, and is a portion of the mouthguard that contacts the second molar when the mouthguard is worn.
[0360] In addition, there are two central incisor parts and two second molar parts in the upper jaw and the lower jaw, respectively, on the right and on the left (that is, there are four in total in the upper jaw and the lower jaw, respectively).
[0361] In the above-mentioned central incisor part and second molar part, in at least one of the central incisor parts and the second molar part, the thickness of the occlusal surface of the central incisor part may be more than 1.5 times the thickness of the occlusal surface of the second molar part, or in all of the central incisor parts and the second molar part, the thickness of the occlusal surface of the central incisor part may be more than 1.5 times the thickness of the occlusal surface of the second molar part, or the average value of the thickness of the occlusal surface of all the central incisor parts may be more than 1.5 times the average value of the thickness of the occlusal surface of all the second molar parts.
[0362] When the thickness of the occlusal surface of the central incisor portion is 1.5 times or more the thickness of the occlusal surface of the second molar portion, the central incisor and the mouth guard can be easily brought into contact during occlusion, and thus there is no need to adjust the occlusion significantly.
[0363] Furthermore, when the thickness of the occlusal surface of the central incisor portion is 5 times or less of the thickness of the occlusal surface of the second molar portion, the second molar can be easily brought into contact with the mouth guard, and thus there is no need to adjust the occlusion significantly.
[0364] Furthermore, the thickness of the occlusal surface of the second molar portion is preferably 0.2 mm to 5 mm, more preferably 0.5 mm to 4 mm.
[0365] When the thickness of the occlusal surface of the second molar portion is 0.2 mm or more, the strength of the mouthguard can be well maintained.
[0366] Furthermore, when the thickness of the occlusal surface of the second molar portion is 5 mm or less, the degree of opening can be suppressed, and discomfort to the wearer can be suppressed.
[0367] The thickness of the occlusal surface refers to the thickness of the mouthguard at the occlusal surface of a specific tooth when the mouthguard is worn. Specifically, it means the shortest distance between the surface contacting the front end of the tooth and the opposite surface opposite to the surface contacting the front end of the tooth in the tooth portion of the mouthguard that contacts the tooth when the mouthguard is worn.
[0368] In other words, the thickness of the occlusal surface means the thickness of the thinnest portion of the mouth guard that is bitten between the teeth when the mouth guard is worn.
[0369] It should be noted that the opposing surface refers to a surface on the mouthguard that is opposite to the surface that contacts the front end of the tooth.
[0370] Figure 1 This is a diagram showing the appearance of a maxillary mouthguard according to an embodiment of the present disclosure.
[0371] like Figure 1 As shown, a maxillary mouthguard 10 according to an embodiment of the present disclosure includes a second molar portion 1 for protecting the maxillary second molars and a central incisor portion 2 for protecting the maxillary central incisors.
[0372] Figure 2 It is a figure which shows the thickness of the maxillary mouthguard of the occlusal surface (flat type) of the central incisor part.
[0373] Figure 3 It is a figure which shows the thickness of the maxillary mouthguard of the occlusal surface (non-planar type) of the central incisor part.
[0374] In addition, when the occlusal surface is a plane, it is called an occlusal surface (planar type). When the occlusal surface is a non-planar surface, it is called an occlusal surface (non-planar type).
[0375] For example, Figure 2 and Figure 3 As shown, the thickness 5 of the occlusal surface of the central incisor portion refers to, when the maxillary mouth guard 10 is worn, in the portion that contacts the central incisor, i.e., the central incisor portion of the maxillary mouth guard 10, the shortest distance between the surface 3 that contacts the front end portion of the central incisor and the opposite surface 4 in the above-mentioned central incisor portion that is opposite to the surface 3 that contacts the front end portion of the central incisor.
[0376] Figure 4 It is a figure which shows the thickness of the maxillary mouthguard in the occlusal surface (flat type) of the second molar part.
[0377] Figure 5 It is a figure which shows the thickness of the maxillary mouthguard at the occlusal surface (non-planar type) of the second molar part.
[0378] For example, Figure 4 and Figure 5As shown, the thickness 8 of the occlusal surface of the second molar portion refers to the shortest distance between the surface 6 contacting the front end portion of the second molar in the second molar portion of the maxillary mouth guard 10, which is the portion in contact with the second molar when the maxillary mouth guard 10 is worn, and the opposite surface 7 in the second molar portion that is opposite to the surface 6 contacting the front end portion of the second molar.
[0379] Furthermore, the mouthguard manufactured by the 3D printer using the method of the first embodiment can freely change its thickness through CAD design, and the wearing feeling can be improved by designing only the molar side surface to be thinner.
[0380] The photocurable composition used in the method for producing the present mouthguard is not limited to the photocurable composition of the first embodiment, and any composition that can be photoshaped may be used.
[0381] The mouthguard manufactured by the method for manufacturing the mouthguard is a device used in the oral cavity, and is a device configured to cover teeth and gums. The manufactured mouthguard is not particularly limited, but is preferably a mouthguard for the upper jaw.
[0382] <<Photocurable composition of the second embodiment>>
[0383] As the photocurable composition of the second embodiment, the following aspects 2a and 2b can be mentioned.
[0384] Method 2a
[0385] The photocurable composition of aspect 2a of the second embodiment includes a (meth)acrylic monomer component and a photopolymerization initiator, and the adhesive force of the cured product is 1.5 N or less, and the Shore A hardness of the cured product is 97 or less.
[0386] The inventors of the present disclosure believe that the cause of discomfort when a cured product obtained by photocuring a photocurable composition (hereinafter, also simply referred to as a cured product) is applied to the human body is the hardness of the cured product.
[0387] For example, when a cured product is used as a dental brace, a strong bite force is applied to the contact surface between the dental brace and the upper and lower teeth through the dental brace due to the bite of the teeth. At this time, if the hardness of the cured product is high, it is believed that the bite force is more easily transmitted to the teeth, thus causing discomfort such as pain.
[0388] On the other hand, the inventors of the present disclosure have found that when the hardness of a cured product is reduced, the adhesive strength of the cured product increases, which is a cause of reduced workability.
[0389] That is, from the viewpoint of suppressing discomfort when applied to the human body and obtaining a cured product with excellent workability, it is important to limit the hardness of the cured product obtained by photocuring the photocurable composition to a range that can suppress discomfort and to suppress the adhesiveness of the cured product.
[0390] The photocurable composition of mode 2a contains a (meth)acrylic monomer component and a photopolymerization initiator, and the adhesion of the cured product is less than 1.5N, and the Shore A hardness of the cured product is less than 97. Therefore, when the photocurable composition of the second embodiment is photocured, the discomfort when applied to the human body can be suppressed, and a cured product with excellent operability can be obtained.
[0391] The preferred range, definition, measurement method and other details of the adhesive force of the cured product of the second embodiment are the same as those described in <Adhesive force of the cured product> of the first embodiment.
[0392] (Hardness of cured product (Shore A hardness))
[0393] The Shore A hardness of the cured product of the photocurable composition of Embodiment 2a is 97 or less.
[0394] When the Shore A hardness of the cured product is 97 or less, discomfort when the cured product is applied to the human body can be suppressed.
[0395] Furthermore, generally, the adhesive force of a cured product tends to increase as the hardness thereof decreases. However, when the photocurable composition of the second embodiment is used, the adhesive force of the cured product can be suppressed even if the hardness of the obtained cured product is 97 or less.
[0396] From the same viewpoint as above, the Shore A hardness of the cured product is preferably 95 or less, more preferably 93 or less.
[0397] Furthermore, the hardness of the cured product of the photocurable composition of embodiment 2a is preferably 50 or more.
[0398] Generally, there is a tendency that the adhesive force of a cured product with a lower hardness (that is, a softer product) is more likely to increase, and when the hardness of the cured product is 50 or more, the adhesive force of the cured product can be more effectively suppressed.
[0399] From the same viewpoint as described above, the hardness of the cured product of the photocurable composition of Embodiment 2a is more preferably 66 or more, and even more preferably 80 or more.
[0400] In addition, in this disclosure, the hardness of a cured product is measured by the following method.
[0401] First, the photocurable composition was irradiated with visible light using a 3D printer, thereby molding the photocurable composition into a shape of 25 mm in length × 25 mm in width × 6 mm in thickness to obtain a molded object (layer width 50 μm). In the above-mentioned irradiation with visible light using a 3D printer, for each layer, the irradiation rate was 5.0 mJ / cm 2 ~10mJ / cm 2 The film is irradiated with visible light having a wavelength of 405 nm under conditions in which the film has a desired thickness within a range of .
[0402] For the above-obtained shaped object, at 10 J / cm 2 The molded object was irradiated with ultraviolet light having a wavelength of 365 nm under the conditions of , thereby obtaining a cured product. The obtained cured product was used as the object of hardness measurement.
[0403] The hardness of the cured product was measured in accordance with ISO 7619-1:2010.
[0404] <Elongation at break of cured product>
[0405] Regarding the photocurable composition of the second embodiment, it is preferable that the elongation at break of a cured product obtained by curing the photocurable composition is 10% or more.
[0406] This can suppress the occurrence of cracks (cracks, breaks, splits, etc.) when an external force is applied to the cured product.
[0407] In addition, by having the elongation at break of the cured product within the above range, the recovery property can be improved (increasing the recovery speed, suppressing the deformation during recovery, etc.), and the recovery property is the performance that the shape of the cured product recovers to the shape before the external force is applied when the external force is removed after the external force is temporarily applied to the cured product. In addition, when the elongation at break of the cured product is within the above range and the adhesion of the cured product is 1.5N or less, the recovery property can be further improved. Furthermore, when the elongation at break of the cured product is within the above range and the adhesion of the cured product is 1.5N or less, the deformation during recovery can be better suppressed.
[0408] From the above viewpoints, the elongation at break of the cured product is preferably 20% or more, more preferably 40% or more, and even more preferably 60% or more.
[0409] In addition, in this disclosure, the elongation at break of a cured product is measured by the following method.
[0410] First, the photocurable composition was irradiated with visible light using a 3D printer to shape the photocurable composition into a dumbbell-shaped test piece conforming to ISO 37-2 to obtain a molded object (laminated width 50 μm).
[0411] In the above-mentioned irradiation of visible light using a 3D printer, for each layer, the irradiation rate was 5.0 mJ / cm 2 ~10mJ / cm 2 The film is irradiated with visible light having a wavelength of 405 nm under conditions in which the film has a desired thickness within a range of .
[0412] For the above-obtained shaped object, at 10 J / cm 2 The molded object was irradiated with ultraviolet light having a wavelength of 365 nm under the conditions of , thereby obtaining a cured product. The obtained cured product was used as the object for measuring the elongation at break.
[0413] The elongation at break of the cured product to be measured was measured using a tensile tester at a tensile speed of 500±50 mm / min in accordance with ISO 37:2017.
[0414] The preferred range, measurement method and other details of the viscosity of the second embodiment are the same as those described in (Viscosity) of the first embodiment.
[0415] Method 2b
[0416] The photocurable composition of mode 2b of the second embodiment comprises a (meth)acrylic monomer component and a photopolymerization initiator, wherein the (meth)acrylic monomer component comprises a (meth)acrylic monomer (A) having two (meth)acryloyl groups and a (meth)acrylic monomer (B) having one (meth)acryloyl group, wherein the molecular weight of the (meth)acrylic monomer (A) per one (meth)acryloyl group is greater than 300 g / mol, at least one of the (meth)acrylic monomer (A) and the (meth)acrylic monomer (B) has an aromatic group, and the Shore A hardness of the cured product is less than 97.
[0417] Hereinafter, each component contained in the photocurable composition in the aspect 2a and the aspect 2b of the second embodiment will be described in detail.
[0418] Details such as specific examples and preferred aspects of the (meth)acrylic monomer component of the second embodiment are the same as those described in <(meth)acrylic monomer component> of the first embodiment.
[0419] Specific examples, preferred aspects, etc. of the (meth)acrylic monomer (A) having two (meth)acryloyl groups of the second embodiment are the same as those described in ((meth)acrylic monomer (A) having two (meth)acryloyl groups) of the first embodiment.
[0420] The preferred range and calculation method of the molecular weight per (meth)acryloyl group in the second embodiment are the same as those described in (Molecular weight per (meth)acryloyl group) in the first embodiment.
[0421] The specific examples, preferred aspects and other details of the (meth)acrylic monomer (B) having one (meth)acryloyl group of the second embodiment are the same as those described in ((meth)acrylic monomer (B) having one (meth)acryloyl group) of the first embodiment.
[0422] In the photocurable composition of the second embodiment, it is preferred that at least one of the (meth)acrylic monomer (A) and the (meth)acrylic monomer (B) has a ring structure.
[0423] Specific examples, preferred aspects and other details of the ring structure in the second embodiment are the same as those of the ring structure that at least one of the (meth)acrylic monomer (A) and the (meth)acrylic monomer (B) may have in the first embodiment.
[0424] In the photocurable composition of the second embodiment, it is preferred that at least one of the (meth)acrylic monomer (A) and the (meth)acrylic monomer (B) has an aromatic group.
[0425] Specific examples, preferred aspects and other details of the aromatic group in the second embodiment are the same as those of the aromatic group that at least one of the (meth)acrylic monomer (A) and the (meth)acrylic monomer (B) may have in the first embodiment.
[0426] In the photocurable composition of the second embodiment, the content of the (meth)acrylic monomer (A) is preferably 250 to 800 parts by mass, and more preferably 350 to 650 parts by mass, relative to 1000 parts by mass of the total content of the (meth)acrylic monomer (A) and the (meth)acrylic monomer (B).
[0427] In the photocurable composition of the second embodiment, the total content of the (meth)acrylic monomer (A) and the (meth)acrylic monomer (B) in the (meth)acrylic monomer component is preferably 90% by mass or more, more preferably 95% by mass or more.
[0428] The photocurable composition of the second embodiment may contain acrylic rubber particles.
[0429] Details such as specific examples and preferred forms of the acrylic rubber particles in the second embodiment are the same as those of the acrylic rubber particles that can be contained in the photocurable composition in the first embodiment.
[0430] In the (meth)acrylic monomer (A) and the (meth)acrylic monomer (B) in the second embodiment, it is preferred that Z in the formula α described in the first embodiment is within the range shown in the item of the formula α described in the first embodiment.
[0431] In the (meth)acrylic monomer (A) and the (meth)acrylic monomer (B) in the second embodiment, it is preferred that Z1 in the formula β described in the first embodiment is within the range shown in the item of the formula β described in the first embodiment.
[0432] The photocurable composition of the second embodiment preferably satisfies at least one of (a) and (b) described in the above-mentioned section of the first embodiment.
[0433] The specific examples, preferred forms, definitions, contents, and other details of (a) and (b) of the (meth)acrylic monomer (A-1), (meth)acrylic monomer (A-2), (meth)acrylic monomer (B-1), and (meth)acrylic monomer (B-2) are the same as the specific examples, preferred forms, definitions, contents, and other details of (a) and (b) of the (meth)acrylic monomer (A-1), (meth)acrylic monomer (A-2), (meth)acrylic monomer (B-1), and (meth)acrylic monomer (B-2) in the first embodiment.
[0434] (Other additives in the (meth)acrylic acid monomer component)
[0435] The (meth)acrylic acid-based monomer component in the second embodiment may contain additives other than the (meth)acrylic acid-based monomer (A) and the (meth)acrylic acid-based monomer (B).
[0436] Specific examples, preferred forms and other details of other additives in the second embodiment are the same as those described in the section (other additives in the (meth)acrylic monomer component) in the first embodiment.
[0437] (Photopolymerization Initiator)
[0438] The photocurable composition of the second embodiment contains a photopolymerization initiator.
[0439] Details such as specific examples and preferred aspects of the photopolymerization initiator in the second embodiment are the same as those of the photopolymerization initiator in the first embodiment.
[0440] <Other ingredients>
[0441] The photocurable composition of the second embodiment may contain one or more components other than the (meth)acrylic monomer (A), the (meth)acrylic monomer (B), and the photopolymerization initiator, as necessary.
[0442] Details such as specific examples and preferred aspects of other components in the second embodiment are the same as those of the first embodiment described above.
[0443] The method for preparing the photocurable composition of the second embodiment is not particularly limited, and an example thereof includes mixing the (meth)acrylic monomer (A), the (meth)acrylic monomer (B), and a photopolymerization initiator (and other components as necessary).
[0444] The details are as described in the above-mentioned first embodiment.
[0445] "Solid Object"
[0446] Details such as specific examples and preferred forms of the cured product of the second embodiment are the same as those described in the "cured product" of the first embodiment.
[0447] <Light Modeling>
[0448] The photocurable composition of the second embodiment is preferably used for photomodeling.
[0449] Regarding the photocurable composition of the second embodiment being for photomodeling, the preferred form, definition and other details thereof are the same as those described in <Photomodeling> of the first embodiment.
[0450] <3D Printer>
[0451] Details such as specific examples and preferred aspects of the 3D printer in the second embodiment are the same as those described in <3D printer> in the first embodiment.
[0452] Dental products
[0453] The photocurable composition of the second embodiment is suitable for producing dental products by photomolding.
[0454] Furthermore, the photocurable composition of the second embodiment is suitable for producing a dental cap, a gum cover, or a lining material by photomolding, and is more suitable for producing a dental cap or a gum cover.
[0455] <Method for manufacturing a mouthguard and a mouthguard>
[0456] When the dental product of the second embodiment is a mouth guard, the mouth guard is preferably manufactured by photomolding.
[0457] The details such as a specific manufacturing method and a preferred embodiment are the same as those described in <Manufacturing method of a mouthguard and a mouthguard> of the first embodiment.
[0458] Example
[0459] Hereinafter, an embodiment of the present disclosure will be described in more detail using examples, but the present disclosure is not limited to these examples.
[0460] 《Example A》
[0461] Example A is an example for more specifically describing the first embodiment of the present disclosure.
[0462] <Preparation of photocurable composition>
[0463] [Examples 1A to 43A, Comparative Examples 2A to 3A]
[0464] The components shown in Tables 1 to 3 below were mixed to obtain photocurable compositions. Table 1 shows the viscosity of each photocurable composition.
[0465] In addition, the said viscosity is measured by the same method as the above-mentioned method.
[0466] [Comparative Example 1A]
[0467] As the photocurable composition, Gingiva Mask (manufactured by NextDent) was used.
[0468] <Evaluation>
[0469] The obtained test pieces were subjected to the following measurements and evaluations. The results are shown in Tables 1 to 3.
[0470] (Elongation at break)
[0471] Using a 3D printer (Kulzer, Cara Print 4.0), the visible light wavelength was 405 nm and the visible light illumination was 8.0 mJ / cm 2The obtained photocurable composition was molded into a dumbbell-shaped test piece conforming to ISO37-2 to obtain a molded product (laminated width 50 μm). 2 Under the conditions of irradiation with ultraviolet light of 365nm wavelength, formal curing is carried out to obtain a light-shaped object (i.e., a cured object).
[0472] The elongation at break of the obtained optically shaped object (hereinafter referred to as a "test piece") was measured in accordance with ISO 37: 2017. These measurements were performed using a tensile tester (manufactured by Shimadzu Corporation) at a tensile speed of 500±50 mm / min.
[0473] (Shore A Hardness)
[0474] Using a 3D printer (Kulzer, Cara Print 4.0), the visible light wavelength was 405 nm and the visible light illumination was 8.0 mJ / cm 2 The obtained photocurable composition was molded into a shape of 25 mm in length × 25 mm in width × 6 mm in thickness to obtain a molded object (laminated width 50 μm). 2 The shaped object is formally cured by irradiating ultraviolet rays with a wavelength of 365 nm under the conditions of , thereby obtaining a light-shaped object (i.e., a cured object).
[0475] The obtained optically molded object (hereinafter referred to as a "test piece") was measured for Shore A hardness in accordance with ISO 7619-1: 2010. The hardness was measured using a Durometer hardness tester (manufactured by Mitutoyo Co., Ltd.), and the value 15 seconds after the needle was inserted was taken as the Shore A hardness value.
[0476] (Adhesion)
[0477] Using a 3D printer (Kulzer, Cara Print 4.0), the visible light wavelength was 405 nm and the visible light illumination was 8.0 mJ / cm 2 The obtained photocurable composition was molded into a shape of 20 mm in length × 20 mm in width × 2 mm in thickness to obtain a molded article (laminated width 50 μm). 2 The shaped object is formally cured by irradiating ultraviolet rays with a wavelength of 365nm under the conditions of , thereby obtaining a light-shaped object.
[0478] The obtained optically shaped object (hereinafter referred to as the "test piece") was attached to the sample stage in a manner that prevented it from loosening. Next, an aluminum probe with a contact area of 10 mm in length and 10 mm in width was brought into contact with the surface of the test piece with a length of 20 mm and a width of 20 mm. The test piece was subjected to a pressure of 0.98 ± 0.01 N / cm2 The contact load is maintained for 1.0±0.1 seconds.
[0479] Then, the probe was peeled off from the contact surface in the vertical direction at a speed of 5±0.5 mm per second using a tensile tester (manufactured by Shimadzu Corporation). Then, the maximum load required to peel off the probe from the contact surface was determined and defined as the adhesive force of the cured product (unit: N).
[0480] (Shock Absorption)
[0481] Using a 3D printer (Kulzer, Cara Print 4.0), the visible light wavelength was 405 nm and the visible light illumination was 8.0 mJ / cm 2 Under the conditions of , the obtained photocurable composition was molded into a shape of 20 mm in length×20 mm in width×3 mm in thickness to obtain a molded article (laminated width 50 μm).
[0482] For the obtained shaped object, by 10J / cm 2 The shaped object is formally cured by irradiating ultraviolet rays with a wavelength of 365nm under the conditions of , thereby obtaining a light-shaped object.
[0483] The obtained optically shaped object (hereinafter referred to as a "test piece") was measured for impact absorption (A (%)) by the above-mentioned method.
[0484] The maximum load was measured using a small tension-compression dual-purpose load cell (LMU-200N, manufactured by IMADA Corporation) connected to a load output device (ZT Digital Force Gauge, manufactured by IMADA Corporation).
[0485] For the test piece held at 37°C for 15 minutes and within 30 seconds, the maximum load was measured at 23°C.
[0486] The free fall of the iron ball takes place in the atmospheric atmosphere.
[0487] (Shape recovery test)
[0488] A 3D printer (Kulzer, Cara Print 4.0) was used at a visible light wavelength of 405 nm and a visible light illumination of 8.0 mJ / cm 2 Under the conditions of , the obtained photocurable composition was molded into a shape of 8 mm in length×39 mm in width×4 mm in thickness to obtain a molded article (laminated width 50 μm).
[0489] For the obtained shaped object, at 10J / cm 2The shaped object is formally cured by irradiating ultraviolet rays with a wavelength of 365nm under the conditions of , thereby obtaining a light-shaped object.
[0490] For the obtained optically shaped object (hereinafter referred to as the "test piece"), stress was applied in such a way that the two ends of the test piece in the long axis direction (transverse axis direction) were in contact with each other to bend the test piece, and the test piece was held for 10 seconds. Then, the stress was released and the shape change of the test piece was observed and evaluated according to the following criteria.
[0491] S: After stress release, it takes 0 seconds or more and less than 1 second to return to the original shape.
[0492] A: After stress is released, it takes more than 1 second and less than 3 seconds to return to the original shape.
[0493] B: After stress release, it takes 3 seconds or more and less than 10 seconds to return to the original shape.
[0494] C: After stress release, the original shape is not restored within 10 seconds, but no cracks or fissures occur.
[0495] D: The test piece cracks within 10 seconds of stress application, and the test piece breaks before the stress is released.
[0496] [Table 1]
[0497]
[0498] [Table 2]
[0499]
[0500] [Table 3]
[0501]
[0502] In Tables 1 to 3, the numbers in the column of "Composition" in each Example and each Comparative Example are expressed in parts by mass.
[0503] In Tables 1 to 3, the expression "AE+B (A and B are arbitrary numbers)" means A×10 B .
[0504] In Tables 1 to 3, the details of each component are as follows.
[0505] <(Meth)acrylic monomer (A) having two (meth)acryloyloxy groups and two urethane bonds>
[0506] The structures of the (meth)acrylic monomers (A) having two (meth)acryloyloxy groups and two urethane bonds described in Tables 1 to 3 are as follows.
[0507] [Chemistry 7]
[0508]
[0509] [Chemistry 8]
[0510]
[0511] UA-160TM Made by Shin-Nakamura Chemical Industry Co., Ltd. Urethane diacrylate monomer with a polyether skeleton
[0512] UA-122P Urethane diacrylate monomer with a polyether skeleton, manufactured by Shin-Nakamura Chemical Industry Co., Ltd.
[0513] UN-6305 Negami Industry Co., Ltd. Urethane diacrylate monomer with a polyether skeleton
[0514] UN-2700 Manufactured by Negami Industry Co., Ltd., urethane diacrylate monomer
[0515] UN-2600 Manufactured by Negami Industry Co., Ltd., urethane diacrylate monomer
[0516] UN-352 Manufactured by Negami Industry Co., Ltd., urethane diacrylate monomer
[0517] UN-333 Negami Industry Co., Ltd. Urethane diacrylate monomer with polyester skeleton
[0518] SUA-01 A compound produced by the method described in the following Production Example 1A, urethane diacrylate monomer
[0519] SUA-02 A compound produced by the method described in the following Production Example 2A, urethane diacrylate monomer
[0520] SUA-03 A compound produced by the method described in the following Production Example 3A, urethane diacrylate monomer
[0521] SUA-04 A compound produced by the method described in the following Production Example 4A, urethane diacrylate monomer
[0522] SUA-05 A compound produced by the method described in the following Production Example 5A, urethane diacrylate monomer
[0523] AH-600 Made by Kyoeisha Chemical Co., Ltd., urethane diacrylate monomer
[0524] MMD-352 A compound produced by the method described in the following Production Example 6A, urethane diacrylate monomer
[0525] Ebecryl8402 and Ebecryl230 manufactured by Daicel-Allnex Corporation, urethane diacrylate monomer
[0526] [Manufacturing Example 1A: Manufacture of SUA-01]
[0527] In a fully dried 1-liter four-necked flask equipped with a stirring blade and a thermometer, 222 g (1.00 mol) of IPDI (isophorone diisocyanate), 0.84 g (0.1 wt% relative to the total weight of IPDI, PEG-1000 and HEA) of DBTDL (dibutyltin dilaurate) and 0.42 g (0.05 wt% relative to the total weight of IPDI, PEG-1000 and HEA) of MEHQ (4-methoxyphenol) were added, stirred until uniform, and then heated to 60°C. Next, 500 g (0.50 mol) of PEG-1000 (molecular weight 1000, manufactured by Toho Chemical Industry Co., Ltd.) was added dropwise over 1 hour. Since the internal temperature rises due to the heat of reaction during the dropwise addition, the dropwise amount was controlled to be below 80°C. After all the drops were added, the reaction temperature was maintained at 80°C and the reaction was carried out for 5 hours.
[0528] Next, the internal temperature of the flask was maintained at 60°C, and 116 g (1.00 mol) of HEA (2-hydroxyethyl acrylate) added to another dropping funnel was added dropwise over 1 hour. Since the internal temperature increased due to the heat of reaction during the dropwise addition, the dropwise addition amount was controlled to be below 80°C. After all the additions were made, the reaction temperature was maintained at 80°C and the reaction was carried out for 5 hours.
[0529] At this time, the progress of the reaction was followed by HPLC analysis to confirm the end point of the reaction. The product was discharged from the reactor to obtain 820 g of urethane acrylate (SUA-01). The viscosity at 40° C. was 31000 mPa·s.
[0530] [Manufacturing Example 2A: Manufacture of SUA-02]
[0531] In a fully dried 1-liter four-necked flask equipped with a stirring blade and a thermometer, 222 g (1.00 mol) of IPDI (isophorone diisocyanate), 0.84 g (0.1 wt% relative to the total weight of IPDI, EXCENOL 1020, and HEA) of DBTDL (dibutyltin dilaurate), and 0.42 g (0.05 wt% relative to the total weight of IPDI, EXCENOL 1020, and HEA) of MEHQ (4-methoxyphenol) were added, stirred until uniform, and then heated to 60°C. Subsequently, 500 g (0.50 mol) of EXCENOL 1020 (molecular weight 1000, manufactured by AGC Chemicals) was added dropwise over 1 hour. Since the internal temperature rises due to the heat of reaction during the dropping process, the amount of dropping was controlled so as to be 80°C or less. After all the additions were made, the reaction temperature was kept at 80°C and the reaction was carried out for 5 hours.
[0532] Next, the internal temperature of the flask was maintained at 60°C, and 116 g (1.00 mol) of HEA (2-hydroxyethyl acrylate) added to another dropping funnel was added dropwise over 1 hour. Since the internal temperature increased due to the heat of reaction during the dropwise addition, the dropwise addition amount was controlled to be below 80°C. After all the additions were made, the reaction temperature was maintained at 80°C and the reaction was carried out for 5 hours.
[0533] At this time, the progress of the reaction was followed by HPLC analysis to confirm the end point of the reaction. The product was discharged from the reactor to obtain 820 g of urethane acrylate (SUA-02) represented by the above formula. The viscosity at 40° C. was 27,000 mPa·s.
[0534] [Manufacturing Example 3A: Manufacture of SUA-03]
[0535] In a fully dried 1-liter 4-necked flask equipped with a stirring blade and a thermometer, add 222 g (1.00 mol) of IPDI (isophorone diisocyanate), 0.87 g (0.1 wt% relative to the total weight of IPDI, PEG-1000 and 4HBA) of DBTDL (dibutyltin dilaurate) and 0.43 g (0.05 wt% relative to the total weight of IPDI, PEG-1000 and 4HBA) of MEHQ (4-methoxyphenol), stir until uniform, and then heat to 60°C. Add 500 g (0.50 mol) of PEG-1000 (molecular weight 1000, manufactured by Toho Chemical Industry Co., Ltd.) dropwise over 1 hour. Since the internal temperature rises due to the heat of reaction during the dropwise addition, the dropwise amount is controlled to be below 80°C. After all the drops are added, the reaction temperature is maintained at 80°C and the reaction is carried out for 5 hours.
[0536] Next, the internal temperature of the flask was maintained at 60°C, and 144 g (1.00 mol) of 4HBA (4-hydroxybutyl acrylate) added to another dropping funnel was added dropwise over 1 hour. Since the internal temperature increased due to the heat of reaction during the dropping process, the amount of dropping was controlled to be below 80°C. After all the additions were made, the reaction temperature was maintained at 80°C and the reaction was carried out for 5 hours.
[0537] At this time, the progress of the reaction was followed by HPLC analysis to confirm the end point of the reaction. The product was discharged from the reactor to obtain 840 g of urethane acrylate (SUA-03) represented by the above formula. The viscosity at 40° C. was 45,000 mPa·s.
[0538] [Manufacturing Example 4A: Manufacture of SUA-04]
[0539] In a fully dried 1-liter four-necked flask equipped with a stirring blade and a thermometer, 222 g (1.00 mol) of IPDI (isophorone diisocyanate), 0.87 g (0.1 wt% relative to the total weight of IPDI, EXCENOL 1020, and 4HBA) of DBTDL (dibutyltin dilaurate), and 0.43 g (0.05 wt% relative to the total weight of IPDI, EXCENOL 1020, and 4HBA) of MEHQ were added, stirred until uniform, and then heated to 60°C. Subsequently, 500 g (0.50 mol) of EXCENOL 1020 (molecular weight 1000, manufactured by AGC Chemicals) was added dropwise over 1 hour. Since the internal temperature rises due to the heat of reaction during the dropping process, the amount of dropping was controlled so as to be 80°C or less. After all the additions were made dropwise, the reaction temperature was maintained at 80°C and the reaction was carried out for 5 hours.
[0540] Next, the internal temperature of the flask was maintained at 60°C, and 144 g (1.00 mol) of 4HBA (4-hydroxybutyl acrylate) added to another dropping funnel was added dropwise over 1 hour. Since the internal temperature increased due to the heat of reaction during the dropping process, the amount of dropping was controlled to be below 80°C. After all the additions were made, the reaction temperature was maintained at 80°C and the reaction was carried out for 5 hours.
[0541] At this time, the progress of the reaction was followed by HPLC analysis to confirm the end point of the reaction. The product was discharged from the reactor to obtain 840 g of urethane acrylate (SUA-04) represented by the above formula. The viscosity at 40° C. was 42,000 mPa·s.
[0542] [Manufacturing Example 5A: Manufacture of SUA-05]
[0543] Into a fully dried 1-liter four-necked flask equipped with a stirring blade and a thermometer, 222 g (1.00 mol) of IPDI (isophorone diisocyanate), 0.87 g (0.1 wt % relative to the total weight of IPDI, PTMG1000 and 4HBA) of DBTDL (dibutyltin dilaurate) and 0.43 g (0.05 wt % relative to the total weight of IPDI, PTMG1000 and 4HBA) of MEHQ (4-methoxyphenol) were added, stirred until uniform, and then heated to 60°C.
[0544] Next, 500 g (0.50 mol) of PTMG1000 (molecular weight 1000, manufactured by Mitsubishi Chemical Corporation) was added dropwise over 1 hour. Since the internal temperature rises due to the heat of reaction during the addition, the amount of addition was controlled to be below 80°C. After all the additions were made, the reaction temperature was maintained at 80°C and the reaction was carried out for 5 hours. Next, the internal temperature of the flask was maintained at 60°C, and 144 g (1.00 mol) of 4HBA (4-hydroxybutyl acrylate) added to another dropping funnel was added dropwise over 1 hour. Since the internal temperature rises due to the heat of reaction during the addition, the amount of addition was controlled to be below 80°C. After all the additions were made, the reaction temperature was maintained at 80°C and the reaction was carried out for 5 hours.
[0545] At this time, the progress of the reaction was followed by HPLC analysis to confirm the end point of the reaction. The product was discharged from the reactor to obtain 840 g of urethane acrylate (SUA-05) represented by the above formula. The viscosity at 40° C. was 38,000 mPa·s.
[0546] [Manufacturing Example 6A: Manufacture of MMD-352]
[0547] In a fully dried 1-liter four-necked flask equipped with a stirring blade and a thermometer, 444 g (2.00 mol) of M-600A (phenyl glycidyl ether acrylate, manufactured by Kyoeisha Chemical Co., Ltd.), 0.63 g of DBTDL (dibutyltin dilaurate) and 0.32 g of MEHQ (4-methoxyphenol) were added, stirred until uniform, and then heated to 60°C. Next, 188 g (1.00 mol) of XDI (meta-xylylene diisocyanate) was added dropwise over 1 hour. Since the internal temperature rises due to the heat of reaction during the dropwise addition, the dropwise amount was controlled to be 80°C or less. After all the drops were added, the reaction temperature was maintained at 80°C and the reaction was carried out for 10 hours.
[0548] At this time, the progress of the reaction was followed by HPLC analysis to confirm the end point of the reaction. The product was discharged from the reactor to obtain 600 g of a urethane diacrylate monomer (MMD-352). The viscosity at 65° C. was 6210 mPa·s.
[0549] <Other (meth)acrylic monomers>
[0550] ((Meth)acrylic monomer having two (meth)acryloyloxy groups and no urethane bond)
[0551] 4EG Dimethacrylate monomer manufactured by Kyoeisha Chemical Co., Ltd.
[0552] [Chemistry 9]
[0553]
[0554] <(Meth)acrylic monomer (B) having one acryloyl group>
[0555] The structures of the (meth)acrylic monomers (B) having one acryloyl group described in Tables 1 to 3 are as follows.
[0556] [Chemistry 10]
[0557]
[0558] PO-A Made by Kyoeisha Chemical Co., Ltd.
[0559] P2H-A Made by Kyoeisha Chemical Co., Ltd.
[0560] POBA manufactured by Kyoeisha Chemical Co., Ltd.
[0561] M-600A Made by Kyoeisha Chemical Co., Ltd.
[0562] M110, M111, M113 Made by Toagosei Co., Ltd.
[0563] HRD01 Made by Nichitoko Techno Fine Chemical Co., Ltd.
[0564] BZ Made by Kyoeisha Chemical Co., Ltd.
[0565] PO Made by Kyoeisha Chemical Co., Ltd.
[0566] LA Made by Kyoeisha Chemical Co., Ltd.
[0567] THF-A Made by Kyoeisha Chemical Co., Ltd.
[0568] <Photopolymerization initiator>
[0569] The structures of the photopolymerization initiators described in Tables 1 to 3 are as follows.
[0570] [Chemistry 11]
[0571]
[0572] Omnirad TPO is manufactured by IGMresins.
[0573] Omnirad819 is manufactured by IGMresins.
[0574] As shown in Tables 1 to 3, in the examples containing a (meth)acrylic monomer component and a photopolymerization initiator, the adhesion of the cured product is 1.5N or less, and the elongation at break of the cured product is 20% or more, a cured product with excellent elongation at break and suppressed adhesion can be obtained.
[0575] In addition, the cured products of the embodiments containing (meth)acrylic monomer components and photopolymerization initiators, having an adhesive force of 1.5 N or less and an elongation at break of 20% or more, have high shape recovery in a shape recovery test, and the generation of cracks and fissures is suppressed.
[0576] In addition, in the examples containing a (meth)acrylic monomer component and a photopolymerization initiator, the adhesion of the cured product is 1.5N or less, and the impact absorption of the cured product is 20% to 80%, a cured product with excellent elongation at break and suppressed adhesion can be obtained.
[0577] In addition, the cured product of the embodiment containing a (meth)acrylic monomer component and a photopolymerization initiator, having an adhesion of 1.5N or less and an impact absorption of 20% to 80%, has high shape recovery in a shape recovery test, thereby suppressing the occurrence of cracks and fissures.
[0578] In the example where the (meth)acrylic monomer component includes a (meth)acrylic monomer (A) having two (meth)acryloyl groups and a (meth)acrylic monomer (B) having one (meth)acryloyl group, a cured product having excellent elongation at break and suppressed adhesive strength can be obtained.
[0579] In addition, the cured product of the embodiment containing a (meth)acrylic monomer component and a photopolymerization initiator, having an adhesion of 1.5N or less and an impact absorption of 20% to 80%, has high shape recovery in a shape recovery test, thereby suppressing the occurrence of cracks and fissures.
[0580] On the other hand, the adhesive force of the cured product obtained in Comparative Example 1A was not suppressed. The elongation at break of the cured products obtained in Comparative Examples 2A and 3A was poor. In addition, the cured products of Comparative Examples 1A to 3A had cracks and fissures in the shape recovery test.
[0581] In addition, Examples 40A and 41A in which (a) the (meth)acrylic monomer (A) includes a (meth)acrylic monomer (A-1) having a molecular weight of 300 g / mol to 600 g / mol per (meth)acryloyl group and a (meth)acrylic monomer (A-2) having a molecular weight of more than 600 g / mol and less than 15,000 g / mol per (meth)acryloyl group, recovered to the original shape in 0 seconds to less than 1 second after stress release, indicating excellent shape recovery.
[0582] (b) Examples 7A, 12A, 14A, 15A and 18A containing a (meth)acrylic monomer (B-1) having two aromatic rings and a (meth)acrylic monomer (B-2) having one aromatic ring recovered to their original shapes in 0 seconds or more and less than 1 second after stress release, indicating excellent shape recovery.
[0583] Examples 38A and 39A satisfying the conditions (a) and (b) recovered to their original shapes in 0 seconds or more and less than 1 second after stress release, indicating that they have excellent shape recovery properties.
[0584] Embodiment B
[0585] Example B is an example for more specifically describing the second embodiment of the present disclosure.
[0586] <Preparation of photocurable composition>
[0587] [Examples 1B to 35B, Comparative Example 2B]
[0588] The components shown in Tables 4 to 7 below were mixed to obtain photocurable compositions. Tables 4 to 7 show the viscosities of the respective photocurable compositions.
[0589] In addition, the said viscosity is measured by the same method as the above-mentioned method.
[0590] [Comparative Example 1B]
[0591] As the photocurable composition, Gingiva Mask (manufactured by NextDent) was used.
[0592] <Evaluation>
[0593] The obtained test pieces were subjected to the following measurements and evaluations. The results are shown in Tables 4 to 7.
[0594] (Elongation at break)
[0595] Using a 3D printer (Kulzer, Cara Print 4.0), the visible light wavelength was 405 nm and the visible light illumination was 8.0 mJ / cm 2 The obtained photocurable composition was molded into a dumbbell-shaped test piece conforming to ISO37-2 to obtain a molded product (laminated width 50 μm). 2 Under the conditions of irradiation with ultraviolet light of 365nm wavelength, formal curing is carried out to obtain a light-shaped object (i.e., a cured object).
[0596] The elongation at break of the obtained optically shaped object (hereinafter referred to as a "test piece") was measured in accordance with ISO 37: 2017. These measurements were performed using a tensile tester (manufactured by Shimadzu Corporation) at a tensile speed of 500±50 mm / min.
[0597] (Shore A Hardness)
[0598] Using a 3D printer (Kulzer, Cara Print 4.0), the visible light wavelength was 405 nm and the visible light illumination was 8.0 mJ / cm 2 The obtained photocurable composition was molded into a shape of 25 mm in length × 25 mm in width × 6 mm in thickness to obtain a molded object (laminated width 50 μm). 2 The shaped object is formally cured by irradiating ultraviolet rays with a wavelength of 365 nm under the conditions of , thereby obtaining a light-shaped object (i.e., a cured object).
[0599] The obtained optically molded object (hereinafter referred to as a "test piece") was measured for Shore A hardness in accordance with ISO 7619-1: 2010. The hardness was measured using a Durometer hardness tester (manufactured by Mitutoyo Co., Ltd.), and the value 15 seconds after the needle was inserted was taken as the Shore A hardness value.
[0600] (Adhesion)
[0601] Using a 3D printer (Kulzer, Cara Print 4.0), the visible light wavelength was 405 nm and the visible light illumination was 8.0 mJ / cm 2 The obtained photocurable composition was molded into a shape of 20 mm in length × 20 mm in width × 2 mm in thickness to obtain a molded article (laminated width 50 μm). 2 The shaped object is formally cured by irradiating ultraviolet rays with a wavelength of 365nm under the conditions of , thereby obtaining a light-shaped object.
[0602] The obtained optically shaped object (hereinafter referred to as the "test piece") was attached to the sample stage in a manner that prevented it from loosening. Next, an aluminum probe with a contact area of 10 mm in length and 10 mm in width was brought into contact with the surface of the test piece with a length of 20 mm and a width of 20 mm. The test piece was subjected to a pressure of 0.98 ± 0.01 N / cm 2 The contact load is maintained for 1.0±0.1 seconds.
[0603] Then, the probe was peeled off from the contact surface in the vertical direction at a speed of 5±0.5 mm per second using a tensile tester (manufactured by Shimadzu Corporation). Then, the maximum load required to peel off the probe from the contact surface was determined and defined as the adhesive force of the cured product (unit: N).
[0604] [Table 4]
[0605]
[0606] [Table 5]
[0607]
[0608] [Table 6]
[0609]
[0610] [Table 7]
[0611]
[0612] In Tables 4 to 7, the numbers in the column "Composition" in each Example and each Comparative Example are expressed in parts by mass.
[0613] In Tables 4 to 7, the expression "AE+B (A and B are arbitrary numbers)" means A×10 B .
[0614] In Tables 4 to 7, the details of each component are as follows.
[0615] <(Meth)acrylic monomer (A) having two (meth)acryloyloxy groups and two urethane bonds>
[0616] The structures of the (meth)acrylic monomers (A) having two (meth)acryloyloxy groups and two urethane bonds described in Tables 4 to 7 are as follows.
[0617] [Chemistry 12]
[0618]
[0619] UA-160TM Made by Shin-Nakamura Chemical Industry Co., Ltd. Urethane diacrylate monomer with a polyether skeleton
[0620] UA-122P Urethane diacrylate monomer with a polyether skeleton, manufactured by Shin-Nakamura Chemical Industry Co., Ltd.
[0621] UN-6305 Negami Industry Co., Ltd. Urethane diacrylate monomer with a polyether skeleton
[0622] UN-2700 Manufactured by Negami Industry Co., Ltd., urethane diacrylate monomer
[0623] UN-2600 Manufactured by Negami Industry Co., Ltd., urethane diacrylate monomer
[0624] UN-352 Manufactured by Negami Industry Co., Ltd., urethane diacrylate monomer
[0625] AH-600 Made by Kyoeisha Chemical Co., Ltd., urethane diacrylate monomer
[0626] MMD-352 A compound produced by the method described in the following Production Example 1B, urethane diacrylate monomer
[0627] Ebecryl8402 and Ebecryl230 manufactured by Daicel-Allnex Corporation, urethane diacrylate monomer
[0628] Ebecryl4859 manufactured by Daicel-Allnex Corporation, urethane diacrylate monomer
[0629] ABE-300 Shin-Nakamura Chemical Industry Co., Ltd., ethoxylated bisphenol A diacrylate
[0630] [Manufacturing Example 1B: Manufacture of MMD-352]
[0631] In a fully dried 1-liter four-necked flask equipped with a stirring blade and a thermometer, 444 g (2.00 mol) of M-600A (phenyl glycidyl ether acrylate, manufactured by Kyoeisha Chemical Co., Ltd.), 0.63 g of DBTDL (dibutyltin dilaurate) and 0.32 g of MEHQ (4-methoxyphenol) were added, stirred until uniform, and then heated to 60°C. Next, 188 g (1.00 mol) of XDI (meta-xylylene diisocyanate) was added dropwise over 1 hour. Since the internal temperature rises due to the heat of reaction during the dropwise addition, the dropwise amount was controlled to be below 80°C. After all the drops were added, the reaction temperature was maintained at 80°C and the reaction was carried out for 10 hours.
[0632] At this time, the progress of the reaction was followed by HPLC analysis to confirm the end point of the reaction. The product was discharged from the reactor to obtain 600 g of a urethane diacrylate monomer (MMD-352). The viscosity at 65° C. was 6210 mPa·s.
[0633] <(Meth)acrylic monomer (B) having one acryloyl group>
[0634] The structures of the (meth)acrylic monomers (B) having one acryloyl group described in Tables 4 to 7 are as follows.
[0635] [Chemistry 13]
[0636]
[0637] PO-A Made by Kyoeisha Chemical Co., Ltd.
[0638] P2H-A Made by Kyoeisha Chemical Co., Ltd.
[0639] POBA manufactured by Kyoeisha Chemical Co., Ltd.
[0640] M-600A Made by Kyoeisha Chemical Co., Ltd.
[0641] M110, M111, M113 Made by Toagosei Co., Ltd.
[0642] HRD01 Made by Nichitoko Techno Fine Chemical Co., Ltd.
[0643] BZ Made by Kyoeisha Chemical Co., Ltd.
[0644] PO Made by Kyoeisha Chemical Co., Ltd.
[0645] LA Made by Kyoeisha Chemical Co., Ltd.
[0646] <Photopolymerization initiator>
[0647] The structures of the photopolymerization initiators described in Tables 4 to 7 are as follows.
[0648] [Chemistry 14]
[0649]
[0650] Omnirad TPO is manufactured by IGMresins Co., Ltd.
[0651] Omnirad819 is manufactured by IGMresins Co., Ltd.
[0652] As shown in Tables 4 to 7, in Examples, cured products having excellent elongation at break and suppressed adhesive strength were obtained.
[0653] On the other hand, the adhesive strength of the cured product obtained in Comparative Example 1B was not suppressed.
[0654] <Manufacturing of mouthguards>
[0655] <Example 1C>
[0656] Use a laboratory dental scanner (Kulzer, Cara Scan4.0) to create three-dimensional impression data of the plaster models and occlusal states of the upper and lower jaws. Upload the respective three-dimensional impression data to CAD design (DENTCA, DENTCAdesign.com). The appearance design of the mouthguard is performed on the software, and the thickness of the occlusal surface of the central incisor is set to 2.5 mm, and the thickness of the occlusal surface of the second molar is set to 1.0 mm (that is, the thickness of the occlusal surface of the central incisor is 2.5 times the thickness of the occlusal surface of the second molar). The three-dimensional modeling data of the target upper jaw mouthguard is obtained through automatic calculation by the algorithm of the software.
[0657] Using a 3D printer (Kulzer, Cara Print 4.0), the visible light wavelength was 405 nm and the visible light illumination was 8.0 mJ / cm 2 Under the conditions of , the photocurable composition of Example 1A was molded using the three-dimensional modeling data of the mouthguard obtained above, thereby obtaining a modeled upper jaw mouthguard.
[0658] For the obtained mouthguard model, at 10J / cm 2 The molded object is formally cured by irradiating ultraviolet rays with a wavelength of 365 nm under the conditions of , thereby obtaining a mouthguard.
[0659] It should be noted that when the obtained mouthguard was fitted into the plaster models of the upper and lower jaws, it was fitted with very good adaptability.
[0660] <Comparative Example 1C>
[0661] The occlusal surface thickness of the central incisor is set to 2.0 mm, and the occlusal surface thickness of the second molar is set to 2.0 mm (i.e., the occlusal surface thickness of the central incisor is 1 times the occlusal surface thickness of the second molar). Other than this, the same operations as in Example 1C are performed, and the three-dimensional modeling data of the target mouthguard is obtained through automatic calculation performed by the algorithm of the software.
[0662] Using a 3D printer (Kulzer, Cara Print 4.0), the visible light wavelength was 405 nm and the visible light illumination was 8.0 mJ / cm 2Under the conditions of , the three-dimensional modeling data of the mouth guard obtained above was used to model the photocurable composition of Example 1B, thereby obtaining a mouth guard modeling object.
[0663] For the obtained mouthguard model, at 10J / cm 2 The molded object is formally cured by irradiating ultraviolet rays with a wavelength of 365 nm under the conditions of , thereby obtaining a mouthguard.
[0664] <Articulator wearing test>
[0665] The mouthguards manufactured by the methods of Example 1C and Comparative Example 1C were worn on an articulator to which plaster models of upper and lower jaws were attached, and were evaluated according to the following criteria.
[0666] ~Evaluation Criteria~
[0667] A: When worn on the articulator, the upper jaw mouthguard can contact the central incisor part of the mandibular plaster model and the second molar part of the mandibular plaster model respectively without the need for bite adjustment.
[0668] B: When worn on the articulator, the upper mouthguard is in contact with the second molar of the mandible on the plaster model, but a gap is created between the upper mouthguard and the central incisor of the mandible on the plaster model, and bite adjustment is required to make them in contact.
[0669] [Table 8]
[0670] Example 1C Comparative Example 1C Evaluation of the occlusal wear test A B
[0671] The entire disclosures of Japanese Patent Application No. 2019-195499 filed on October 28, 2019, Japanese Patent Application No. 2019-195500 filed on October 28, 2019, and Japanese Patent Application No. 2020-071833 filed on April 13, 2020 are incorporated into this specification by reference.
[0672] All documents, patent applications, and technical standards described in this specification are incorporated herein by reference to the same extent as if each individual document, patent application, and technical standard was specifically and individually described as being incorporated by reference.
Claims
1. A photocurable composition comprising a (meth)acrylic monomer component and a photopolymerization initiator, The (meth)acrylic monomer component includes a (meth)acrylic monomer A having two (meth)acryloyl groups and a (meth)acrylic monomer B having one (meth)acryloyl group. The total content of the (meth)acrylic acid monomer A and the (meth)acrylic acid monomer B in the (meth)acrylic acid monomer component is 90% by mass or more, The (meth)acrylic monomer A has a molecular weight of 300 g / mol or more per (meth)acryloyl group, and the (meth)acrylic monomer A includes a compound represented by the following formula (1): [Chemistry 1] In formula (1), R 1 Each independently represents a divalent linking group, R 2 Each independently represents a divalent chain hydrocarbon group having 2 to 6 carbon atoms which may have a substituent, R 3 are each independently a methyl group or a hydrogen atom, At least one of the (meth)acrylic monomer A and the (meth)acrylic monomer B has an aromatic group, The aromatic ring concentration in the (meth)acrylic acid monomer component is 0.00100 mol / g or more, The aromatic ring concentration in the (meth)acrylic monomer A is 0.0020 mol / g or less, In the photocurable composition, Z1 in the following formula β is 5×10 3 ~500×10 4 , Z1=X1 / Y1 Formula β X1 (g / mol): molecular weight of the (meth)acrylic monomer A per (meth)acryloyl group, Y1 (mol / g): The aromatic ring concentration in the (meth)acrylic monomer component. 2 . The photocurable composition according to claim 1 , wherein the adhesive force of the cured product thereof is 1.5 N or less, and the elongation at break of the cured product is 20% or more. 3 . The photocurable composition according to claim 2 , wherein the elongation at break of the cured product is 40% or more. 4 . The photocurable composition according to claim 1 , wherein the adhesive force of the cured product thereof is 1.5 N or less, and the impact absorbency of the cured product is 20% to 80%. 5 . The photocurable composition according to claim 4 , wherein the impact absorbency of the cured product is 20% to 70%. 6 . The photocurable composition according to claim 4 , wherein the elongation at break of the cured product is 20% or more. 7 . The photocurable composition according to claim 1 , wherein the adhesive force of the cured product thereof is 1.5 N or less, and the Shore A hardness of the cured product is 97 or less. 8 . The photocurable composition according to claim 1 , wherein the content of the (meth)acrylic monomer A is 250 to 800 parts by mass based on 1000 parts by mass of the total content of the (meth)acrylic monomer A and the (meth)acrylic monomer B.
9. The photocurable composition according to claim 1, wherein R 1 is a divalent chain hydrocarbon group, or is a group consisting of a divalent chain hydrocarbon group and at least one group selected from the group consisting of a divalent hydrocarbon group having an alicyclic structure, a divalent hydrocarbon group having an aromatic structure, and a divalent group containing a heteroatom, The divalent hydrocarbon group having an aromatic structure is a divalent hydrocarbon group represented by the following formula (1-a): [Chemistry 2] In formula (1-a), * represents a binding position.
10. The photocurable composition according to claim 1, wherein R 1 It is a divalent chain hydrocarbon group, or a group consisting of a divalent chain hydrocarbon group and at least one group selected from the group consisting of a divalent hydrocarbon group having an alicyclic structure and a divalent group containing a heteroatom.
11. The photocurable composition according to claim 9, wherein R 1 The heteroatom-containing divalent group in includes at least one bond selected from the group consisting of a urethane bond and an ether bond.
12. The photocurable composition according to claim 1, which satisfies at least one of the following (a) and (b), (a) the (meth)acrylic monomer A comprises a (meth)acrylic monomer A-1 having a molecular weight of 300 g / mol to 600 g / mol per (meth)acryloyl group, and a (meth)acrylic monomer A-2 having a molecular weight of more than 600 g / mol to 15000 g / mol per (meth)acryloyl group, (b) The (meth)acrylic monomer B includes a (meth)acrylic monomer B-1 having two aromatic rings and a (meth)acrylic monomer B-2 having one aromatic ring. 13 . The photocurable composition according to claim 1 , wherein the aromatic ring concentration in the (meth)acrylic monomer A is 0.0016 mol / g or less.
14. The photocurable composition according to claim 1, wherein Z1 is 1×10 4 ~100×10 4 . 15 . The photocurable composition according to claim 2 , wherein the viscosity of the composition measured by an E-type viscometer at 25° C. and 50 rpm is 10 mPa·s to 5000 mPa·s. The photocurable composition according to claim 1 , which is for photomodeling.
17. The photocurable composition according to claim 1, which is used for producing a dental product by photomodeling.
18. The photocurable composition according to claim 1, which is used for producing a dental cap, a gum cover or a lining material by photomodeling. 19 . A dental product comprising a cured product of the photocurable composition according to claim 1 .
20. The dental product according to claim 19, which is for use in a dental crown, a gum mask or a lining material.
